Composition, electrode, battery, and electrode active material

A sulfur-modified polyacrylonitrile-based composition with controlled alcohol content addresses the capacity loss and coating issues in lithium-ion battery electrodes, ensuring stable performance through enhanced coating properties and reduced capacity degradation.

JP2025020057AInactive Publication Date: 2025-02-10ADEKA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2021183911
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-11-11
Publication Date
2025-02-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Conventional electrodes for lithium-ion secondary batteries suffer from significant reductions in charge and discharge capacity due to repeated charging and discharging, and they also lack adequate coating properties.

Method used

A composition containing sulfur-modified polyacrylonitrile, alcohol, and water is formulated with a specific alcohol content ratio of 0.1% to 50% by mass, which is used to form an electrode active material layer, incorporating a conductive aid and binder to enhance coating properties and stability.

Benefits of technology

The composition results in electrodes and batteries with improved coating properties and minimal decrease in charge and discharge capacity even after repeated cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020057000004
    Figure 2025020057000004
  • Figure 2025020057000005
    Figure 2025020057000005
  • Figure 2025020057000006
    Figure 2025020057000006
Patent Text Reader

Abstract

To provide a composition which has good coatability and can be used to manufacture an electrode and a battery which exhibit little decrease in charge / discharge capacity even after repeated charge / discharge.SOLUTION: A composition contains sulfur-modified polyacrylonitrile, alcohol, and water, and the content of the alcohol is 0.1 mass% to 50 mass% based on the total amount of the alcohol and the water.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition containing sulfur-modified polyacrylonitrile, water and an alcohol, an electrode and a battery using the composition, and an electrode active material. [Background technology]

[0002] Lithium-ion secondary batteries are small, lightweight, have high energy density, high capacity, and can be repeatedly charged and discharged, so they are increasingly being used in portable electronic devices such as smartphones, portable personal computers, and handy video cameras, as well as electric vehicles and hybrid vehicles that use electricity as part of their power source.

[0003] The characteristics of a lithium-ion secondary battery depend on its constituent materials, such as electrodes, separators, and electrolytes, and research and development of each of these components is being actively conducted. For example, electrodes are composed of materials such as binders, current collectors, conductive assistants, and electrode active materials, and research and development of electrode active materials in particular is being actively conducted.

[0004] An organic sulfur-based electrode active material obtained by heat-treating a mixture of an organic compound and sulfur in a non-oxidizing atmosphere is known as an electrode active material that has a large charge / discharge capacity and is less susceptible to deterioration in charge / discharge capacity due to repeated charge / discharge cycles.

[0005] A composition containing an electrode active material and the like is coated on a current collector and used as an electrode for a lithium ion secondary battery. Such a composition is produced by mixing an electrode active material for storing electric energy, a conductive assistant for imparting electric conductivity, and a binder for adhering these components to the current collector with water or an organic solvent. Examples of such compositions include those described in Patent Documents 1 and 2 and Non-Patent Document 1. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Special Publication No. 2021-509529 [Patent Document 2] Special Publication No. 2020-527827 [Non-patent literature]

[0007] [Non-Patent Document 1] “Reinforcement of an electrically conductive network with ethanol as a dispersing agent in the slurry preparation step” Jiwon Jung, Jihyun Jang, OB Chae, Taeho Yoon, Ji Heon Ryu, Seung M. Oh, Journal of Power Sources, Vol. 287 (2015), 359-362 Summary of the Invention [Problem to be solved by the invention]

[0008] However, electrodes manufactured using conventional compositions have a problem that the charge / discharge capacity significantly decreases with repeated charge / discharge cycles, and there has been a demand for improvements. In addition, there has been a demand for compositions with excellent coatability.

[0009] An object of the present invention is to provide a composition which has good coatability and can be used to produce electrodes and batteries which exhibit little decrease in charge-discharge capacity even after repeated charge-discharge cycles. [Means for solving the problem]

[0010] As a result of intensive research into the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by setting the alcohol content in a composition containing sulfur-modified polyacrylonitrile, alcohol and water to a specific ratio, and have completed the present invention.

[0011] That is, the present invention is represented by the following [1] to

[10] .

[0012] [1] A composition comprising sulfur-modified polyacrylonitrile, alcohol, and water, the alcohol content being 0.1% by mass to 50% by mass with respect to the total amount of the alcohol and water. [2] The composition according to [1], wherein the alcohol has 1 to 5 carbon atoms. [3] The composition according to [1] or [2], comprising, per 100 parts by mass of the composition, 15 to 70 parts by mass of sulfur-modified polyacrylonitrile and 30 to 80 parts by mass of alcohol and water in total. [4] The composition according to any one of [1] to [3], further comprising, per 100 parts by mass of the composition, 0.1 parts by mass to 30 parts by mass of a conductive assistant. [5] The composition according to any one of [1] to [4], further comprising 0.2 parts by mass to 18 parts by mass of a binder per 100 parts by mass of the composition. [6] The composition according to [5], wherein the binder is an aqueous binder. [7] The composition according to any one of [1] to [6], which is for forming an electrode active material layer.

[0013] [8] An electrode having an electrode active material layer formed using the composition according to [7].

[0014] [9] A battery comprising the electrode according to [8], a counter electrode, and a non-aqueous electrolyte.

[0015]

[10] An electrode active material comprising sulfur-modified polyacrylonitrile, which is added to a composition containing alcohol and water, wherein the content of the alcohol in the composition is 0.1% by mass to 50% by mass with respect to the total amount of the alcohol and the water. Effect of the Invention

[0016] According to the present invention, it is possible to provide a composition which has good coatability and can be used to produce an electrode and a battery which exhibit little decrease in charge / discharge capacity even after repeated charge / discharge. [Brief description of the drawings]

[0017] [Figure 1] FIG. 1 is a longitudinal sectional view that illustrates an example of the structure of a coin-type battery of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing the basic structure of a cylindrical battery of the present invention. [Diagram 3] FIG. 2 is a perspective view showing a cross section of the internal structure of a cylindrical battery of the present invention. [Figure 4] FIG. 2 is an exploded perspective view showing a stacked electrode group inside a laminated battery of the present invention. [Diagram 5] FIG. 1 is an exploded perspective view showing a typical laminated battery of the present invention. [Figure 6] FIG. 1 is an external plan view showing a typical laminate type battery of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The composition, electrode, battery, and electrode active material of the present invention will be described in detail below based on preferred embodiments.

[0019] In this specification, "volume %" refers to a volume percentage measured in an environment of 23°C.

[0020] In this specification, the average particle size refers to the 50% particle size measured by a laser diffraction light scattering method. In the laser diffraction light scattering method, the particle size is a volume-based diameter, and the secondary particle size of the measurement object is measured. When measuring the average particle size by the laser diffraction light scattering method, the measurement is performed in a state where the measurement object is dispersed in water, alcohol, or a mixture thereof.

[0021] A. Composition First, the composition of the present invention will be described.

[0022] The composition of the present invention contains sulfur-modified polyacrylonitrile, alcohol, and water, and the content of the alcohol is 0.1% by mass to 50% by mass based on the total amount of the alcohol and water.

[0023] A1. Sulfur-modified polyacrylonitrile The composition of the present invention contains sulfur-modified polyacrylonitrile (hereinafter, sometimes referred to as "SPAN"). In the present invention, SPAN includes sulfur atoms and a polyacrylonitrile compound and can be used as an electrode active material. In SPAN, the sulfur atoms and the polyacrylonitrile compound may be in a stable bonded state, and for example, some of the sulfur atoms may form covalent bonds with atoms constituting the polyacrylonitrile compound or may be physically adsorbed to the polyacrylonitrile compound. Such SPAN can be produced by mixing a polyacrylonitrile compound with sulfur and modifying the mixture by heat treatment in a non-oxidizing atmosphere at 250° C. to 600° C. The non-oxidizing atmosphere refers to an atmosphere having an oxygen concentration of less than 5% by volume, preferably less than 2% by volume, and more preferably substantially no oxygen, and examples of such an atmosphere include an inert gas atmosphere such as nitrogen, helium, or argon, a sulfur gas atmosphere, or a hydrogen sulfide gas atmosphere.

[0024] The method of heating the mixture of the polyacrylonitrile compound and sulfur to 250° C. to 600° C. can be appropriately selected, and for example, a heating device such as a device for heating or heating and pressurizing with a roll, an oven dryer, a far-infrared heater, a dry heat dryer, a hot air dryer, an infrared radiation heating device, a high-frequency induction heating device, an electric furnace, a gas furnace, etc. During the heat treatment, the heating may be performed under pressurized or reduced pressure conditions, or in an inert gas atmosphere such as argon or nitrogen.

[0025] The polyacrylonitrile compound may be a homopolymer of acrylonitrile or a copolymer of acrylonitrile and another monomer. When the content of acrylonitrile in the polyacrylonitrile compound is a predetermined amount or more, it is easy to increase the capacity of the battery. From the viewpoint of excellent battery performance, the content of acrylonitrile in the copolymer of acrylonitrile and another monomer is preferably at least 90 mass%, and polyacrylonitrile homopolymer is more preferable. Examples of the other monomer include acrylic acid, vinyl acetate, N-vinylformamide, and N,N'-methylenebis(acrylamide).

[0026] It is preferable that SPAN is pulverized to a desired particle size by a method such as pulverization or granulation. The pulverization may be a dry pulverization carried out in a gas or a wet pulverization carried out in a liquid such as water. Examples of industrial pulverization methods include a ball mill, a roller mill, a turbo mill, a jet mill, a cyclone mill, a hammer mill, a pin mill, a rotary mill, a vibration mill, a planetary mill, an attritor, and a bead mill.

[0027] The crushed SPAN is preferably further classified. The classification method is not particularly limited, but may be a dry classification method such as gravity classification, inertial classification, or centrifugal classification; a wet classification method such as sedimentation classification, mechanical classification, or hydraulic classification; or a sieving classification method using a sieve such as a vibrating sieve or an in-plane motion sieve. Among these, the sieving classification method is preferred. By carrying out the crushing and classification steps, SPAN having a particle size suitable for use in forming a battery electrode can be efficiently produced.

[0028] The average particle diameter (D50) of SPAN is preferably 50 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less. The average particle diameter (D50) of SPAN is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1 μm or more. By setting the average particle diameter (D50) of SPAN within the above-mentioned range, the handleability of SPAN is improved, and the coatability of the composition of the present invention is improved, so that the electrode surface can be easily smoothed. In addition, the charge and discharge stability of the obtained electrode and battery is improved, and the decrease in charge and discharge capacity is reduced even when charging and discharging is repeated.

[0029] The average particle size of SPAN is expressed as the 50% particle size measured by the laser diffraction light scattering method. In the laser diffraction light scattering method, the particle size is the volume-based diameter, and the secondary particle size of SPAN is measured. When measuring the average particle size of SPAN by the laser diffraction light scattering method, SPAN is dispersed in a dispersion medium such as water or alcohol and then measured.

[0030] In the present invention, the shape of the SPAN may be fibrous. The average fiber diameter of the fibrous SPAN is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.15 μm or more. The average fiber diameter of the fibrous SPAN is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 2 μm or less. By setting the average fiber diameter of the SPAN within the above range, the coating property of the composition of the present invention becomes better, and the electrode surface can be easily made smooth. In addition, the charge / discharge capacity of the obtained electrode and battery becomes large, and the decrease in the charge / discharge capacity is less even when the charge / discharge is repeated.

[0031] When the aspect ratio of the fibrous SPAN is expressed as the ratio of fiber length / fiber diameter, the average aspect ratio of the fibrous SPAN is preferably 2 or more, more preferably 3 or more, and even more preferably 5 or more. The average aspect ratio of the fibrous SPAN is preferably 300 or less, more preferably 200 or less, and even more preferably 150 or less. By setting the average aspect ratio of the fibrous SPAN within the above-mentioned range, the coating property of the composition of the present invention becomes better, and the electrode surface can be easily made smooth. In addition, the charge / discharge capacity of the obtained electrode and battery becomes large, and the decrease in the charge / discharge capacity is less even when the charge / discharge is repeated.

[0032] The fiber length and fiber diameter of fibrous SPAN can be determined from scanning electron microscope images (SEM images). Fiber length indicates the length of the fiber, and fiber diameter indicates the diameter of the circle if the cross section perpendicular to the longitudinal direction of the fiber is circular, and indicates the average of the short and long diameters of the cross section if the cross section is not circular. The fiber diameter of one fibrous SPAN can be measured at any location. The average aspect ratio of fibrous SPAN is the value calculated by dividing the average fiber length by the average fiber diameter. The average fiber length and average fiber diameter of fibrous SPAN indicate the number average values ​​of the fiber diameter and fiber length measured from SEM images of 10 or more fibrous SPAN.

[0033] The content of sulfur in SPAN is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 35% by mass or more. The content of sulfur in SPAN is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less. By setting the content of sulfur in SPAN within the above range, the coatability of the composition of the present invention becomes better. In the electrode and the battery obtained by using the composition of the present invention, the decrease in the charge and discharge capacity is less even when the charge and discharge are repeated. In addition, when the composition of the present invention is used in a lithium ion secondary battery, a large charge and discharge capacity and excellent cycle characteristics are obtained.

[0034] In this specification, the sulfur content in SPAN represents a value calculated from the results of elemental analysis using a CHN analyzer capable of analyzing sulfur and oxygen, such as vario MICRO cube manufactured by Elementor.

[0035] In the composition of the present invention, the content of SPAN is not particularly limited as long as it can solve the problem of the present invention. The content of SPAN is preferably 15 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 25 parts by mass or more, and most preferably 30 parts by mass or more, relative to 100 parts by mass of the composition. The content of SPAN is preferably 70 parts by mass or less, more preferably 68 parts by mass or less, even more preferably 65 parts by mass or less, even more preferably 50 parts by mass or less, and most preferably 40 parts by mass or less. By setting the content of SPAN within the above range, the coatability of the composition of the present invention is improved. In addition, the charge / discharge capacity of the electrode and battery obtained using the composition of the present invention is reduced even when the charge / discharge is repeated.

[0036] A2. Alcohol and water Since the above-mentioned SPAN is a substance with low polarity, it is difficult to mix with water or a binder with high polarity. The composition of the present invention contains a specific amount of an amphiphilic alcohol in order to improve the dispersibility of SPAN.

[0037] The alcohol is preferably an alcohol having 1 to 5 carbon atoms, more preferably ethanol, propanol, and isopropanol, and even more preferably ethanol. By using such an alcohol, the coating property of the composition of the present invention is improved, and the alcohol is unlikely to evaporate and remain in the electrode during the production of the electrode, making it easier to form a lightweight electrode and an electrode with low internal resistance. In addition, the charge / discharge capacity of the electrode and battery obtained by using the composition of the present invention is less likely to decrease even when the electrodes and batteries are repeatedly charged and discharged.

[0038] In the composition of the present invention, the content of the alcohol is 0.1% by mass to 50% by mass based on the total of the alcohol and water. The content of the alcohol is preferably 1% by mass or more based on the total of the alcohol and water, more preferably 3% by mass or more, even more preferably 5% by mass or more, and most preferably 8% by mass or more. The content of the alcohol is preferably 30% by mass or less based on the total of the alcohol and water, more preferably 20% by mass or less, and most preferably 15% by mass or less. By setting the content of the alcohol within the above range, the dispersibility of the SPAN contained in the composition of the present invention is greatly improved, and the coatability of the composition of the present invention becomes better. In addition, the charge / discharge capacity of the electrode and battery obtained by using the composition of the present invention is less decreased even when the charge / discharge is repeated.

[0039] The total content of alcohol and water in the composition of the present invention is preferably 30 parts by mass or more, more preferably 35 parts by mass or more, even more preferably 40 parts by mass or more, even more preferably 50 parts by mass or more, and most preferably 55 parts by mass or more, relative to 100 parts by mass of the composition. The total content of alcohol and water is preferably 80 parts by mass or less, more preferably 70 parts by mass or less, and even more preferably 65 parts by mass or less, relative to 100 parts by mass of the composition. By setting the total content of alcohol and water within the above range, the dispersibility of SPAN contained in the composition of the present invention is greatly improved, and the coatability of the composition of the present invention becomes better. In addition, the charge / discharge capacity of the obtained electrode and battery is less likely to decrease even when the charge / discharge cycle is repeated.

[0040] The composition of the present invention contains alcohol and water, and therefore the composition of the present invention can be used as an aqueous slurry. The composition of the present invention has excellent coatability, and a layer (active material layer) containing SPAN can be formed by drying or baking the composition to remove the alcohol and water. The composition of the present invention is preferably used for forming an electrode active material layer, particularly for forming an electrode active material layer for a secondary battery, and particularly for forming an electrode active material layer for a lithium ion secondary battery. By forming an electrode active material layer using the composition of the present invention, an electrode and a battery that exhibit little decrease in charge / discharge capacity even when repeatedly charged and discharged can be easily manufactured.

[0041] A3. Other ingredients The composition of the present invention may contain other components within a range that does not adversely affect the effects of the present invention. Examples of other components include active materials other than SPAN, binders, conductive assistants, organic solvents, viscosity modifiers, reinforcing materials, leveling agents, antioxidants, pH adjusters, and the like. In addition, these components may be used alone or in combination of two or more types in any ratio. The total content of the other components may be 50 parts by mass or less, preferably 1 part by mass or more and 30 parts by mass or less, more preferably 2 parts by mass or more and 20 parts by mass or less, and even more preferably 3 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the composition of the present invention. By setting the total content of the other components within the above range, the coatability of the composition of the present invention is improved, and the charge / discharge capacity is less likely to decrease even if the electrode and battery obtained using the composition of the present invention are repeatedly charged and discharged.

[0042] A3-1. Active materials other than SPAN The composition of the present invention may contain a known active material used in an electrode material. Specific examples of the active material include lithium-containing transition metal complex oxides, lithium-containing transition metal phosphate compounds, lithium-containing silicate compounds, lithium-containing transition metal sulfate compounds, sulfur-modified elastomer compounds, sulfur-modified polyether compounds, sulfur-modified pitch compounds, sulfur-modified polynuclear aromatic ring compounds, sulfur-modified aliphatic hydrocarbon oxides, polythienoacene compounds, sulfur-modified polyamide compounds, polycarbon sulfide, sulfur-carbon complexes, sulfur, and sulfur materials described in the section "Synthesis of lithium-sulfur battery positive electrode active material by direct reaction of elemental sulfur and organic matter" in the Journal of the Society of Organic Synthesis Chemistry (Vol. 78, No. 6, 2020, p. 627-629).

[0043] From the viewpoint of obtaining good battery characteristics when the composition of the present invention is used in a battery, the lithium-containing transition metal composite oxide is preferably a compound in which the transition metal is vanadium, titanium, chromium, manganese, iron, cobalt, nickel, or copper.Specific examples of the lithium-containing transition metal composite oxide include lithium cobalt composite oxides such as LiCoO2, lithium nickel composite oxides such as LiNiO2, lithium manganese composite oxides such as LiMnO2, LiMn2O4, and Li2MnO3, and compounds in which a part of the transition metal atoms that are the main components of these lithium transition metal composite oxides are replaced with other metals (e.g., aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, lithium, nickel, copper, zinc, magnesium, gallium, zirconium, etc.).

[0044] Examples of lithium transition metal composite oxides in which a part of the main transition metal atoms is replaced with other metals include Li 1.1 Mn 1.8 Mg 0.1 O4, Li 1.1 Mn 1.85 Al 0.05 O4, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.5 Mn0.5 O2, LiNi 0.80 Co 0.17 Al 0.03 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiMn 1.8 Al 0.2 O4, LiNi 0.5 Mn 1.5 O4, Li2MnO3-LiMO2 (M = Co, Ni, Mn), etc.

[0045] From the viewpoint of obtaining good battery characteristics when the composition of the present invention is used in a battery, the transition metal of the lithium-containing transition metal phosphate compound is preferably vanadium, titanium, manganese, iron, cobalt, nickel, etc. Specific examples of the lithium-containing transition metal phosphate compound include LiFePO4, LiM x Fe 1-x Examples of such lithium-containing iron phosphate compounds include lithium-containing cobalt phosphate compounds such as LiCoPO4 (M = Co, Ni, Mn; 0 < x < 1), lithium-containing transition metal phosphate compounds in which some of the transition metal atoms that make up the main part of these lithium-containing transition metal phosphate compounds have been replaced with other metals such as aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, lithium, nickel, copper, zinc, magnesium, gallium, zirconium, and niobium, and lithium-containing vanadium phosphate compounds such as Li3V2(PO4)3.

[0046] Specific examples of the lithium transition metal phosphate compound include LiFePO4, LiMn X1 Fe 1-X1 PO4, LiCuPO4, LiNiPO4, LiCoPO4, LiMnPO4, LiVOPO4, Li2FePO4, Li2NiPO4, Li2CoPO4, Li2MnPO4, Li2NiPO4F, Li2CoPO4F, Li2MnPO4F, Li2FePO4F, Li3V2(PO4)3, LiMn 7 / 8Fe 1 / 8 PO4, LiMn 2 / 3 Fe 1 / 3 PO4, LiFe 0.9 Mn 0.1 PO4, LiFe 0.2 Mn 0.8 PO4, LiFe 0.15 Mn 0.75 Mg 0.1 PO4, LiFe 0.19 Mn 0.75 Zr 0.03 Examples include PO4 and the like. X1 represents 0 < X1 ≤ 0.5.

[0047] From the viewpoint of good charge-discharge stability, LiFePO4, LiCuPO4, LiNiPO4, LiCoPO4, LiMnPO4, and LiVOPO4 are preferred, and LiFePO4, LiNiPO4, LiCoPO4, and LiMnPO4 are more preferred.

[0048] Examples of the lithium-containing silicate compound include Li2FeSiO4 and the like.

[0049] Examples of the lithium-containing transition metal sulfate compound include LiFeSO4, LiFeSO4F, and the like.

[0050] Examples of the sulfur-modified elastomer compound include those obtained by heat-treating a mixture of an elastomer and sulfur in a non-oxidizing atmosphere. Examples of the elastomer include natural rubber, isoprene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, and the like. The elastomer is preferably acrylonitrile-butadiene rubber. Since sulfur remaining after the heat treatment causes a decrease in the cycle characteristics of the secondary battery, it is preferably removed from the sulfur-modified elastomer compound by, for example, heating or solvent washing. The heat treatment is preferably carried out in a temperature range of 300°C to 500°C. From the viewpoint of obtaining a large charge-discharge capacity, the sulfur content in the sulfur-modified elastomer compound is preferably 30% by mass to 75% by mass, and more preferably 40% by mass to 70% by mass.

[0051] The sulfur-modified polyether compound may be obtained by subjecting a mixture of a polyether compound and sulfur to a heat treatment in a non-oxidizing atmosphere. Examples of the polyether compound include polyethylene glycol, polypropylene glycol, ethylene oxide / propylene oxide copolymer, and polytetramethylene glycol. The polyether compound may have an alkyl ether group, an alkylphenyl ether group, or an acyl group at its terminal, or may be an ethylene oxide adduct of a polyol such as glycerin or sorbitol. Since the sulfur remaining after the heat treatment is a factor that reduces the cycle characteristics of a secondary battery, it is preferable to remove it from the sulfur-modified polyether compound by, for example, heating or solvent washing. The heat treatment is preferably performed in a temperature range of 300° C. to 500° C. The content of sulfur in the sulfur-modified polyether compound is preferably 30% by mass to 75% by mass, more preferably 40% by mass to 70% by mass, from the viewpoint of obtaining a large charge / discharge capacity.

[0052] The sulfur-modified pitch compound is obtained by heat-treating a mixture of pitches and sulfur in a non-oxidizing atmosphere. Examples of pitches include petroleum pitch, coal pitch, mesophase pitch, asphalt, coal tar, coal tar pitch, organic synthetic pitch obtained by polycondensation of condensed polycyclic aromatic hydrocarbon compounds, and organic synthetic pitch obtained by polycondensation of heteroatom-containing condensed polycyclic aromatic hydrocarbon compounds. Pitches are a mixture of various compounds and include condensed polycyclic aromatics. The condensed polycyclic aromatics contained in pitches may be of a single type or may be of multiple types. The condensed polycyclic aromatics may contain nitrogen atoms and sulfur atoms in addition to carbon and hydrogen in the ring. The sulfur remaining after the heat treatment is a factor that reduces the cycle characteristics of the secondary battery, so it is preferable to remove it from the sulfur-modified pitch compound by, for example, heating or solvent washing. The heat treatment is preferably performed at a temperature range of 300°C to 500°C. The sulfur content in the sulfur-modified pitch compound is preferably 20% by mass to 75% by mass, and more preferably 25% by mass to 70% by mass, from the viewpoint of obtaining a large charge / discharge capacity.

[0053] The sulfur-modified polynuclear aromatic ring compound is obtained by heating a mixture of sulfur and a benzene-based aromatic ring compound such as naphthalene, anthracene, tetracene, pentacene, phenanthrene, chrysene, picene, pyrene, benzopyrene, perylene, or coronene in a non-oxidizing atmosphere. In addition, examples of the sulfur-modified polynuclear aromatic ring compound include aromatic ring compounds in which a part of the benzene-based aromatic ring compound is a 5-membered ring, and heteroatom-containing heteroaromatic ring compounds in which a part of the carbon atoms of the aromatic ring compound is replaced with sulfur, oxygen, nitrogen, or the like. Furthermore, these polynuclear aromatic ring compounds may have a substituent such as a linear or branched alkyl group having 1 to 12 carbon atoms, an alkoxyl group, a hydroxyl group, a carboxyl group, an amino group, an aminocarbonyl group, an aminothio group, a mercaptothiocarbonylamino group, or a carboxyalkylcarbonyl group. The sulfur remaining after the heat treatment is a factor that reduces the cycle characteristics of a secondary battery, and is therefore preferably removed from the sulfur-modified polynuclear aromatic ring compound by, for example, heating or solvent washing. The heat treatment is preferably carried out in the temperature range of 250° C. to 550° C. The sulfur content in the sulfur-modified polynuclear aromatic ring compound is preferably 35% by mass to 75% by mass, and more preferably 40% by mass to 70% by mass, from the viewpoint of obtaining a large charge / discharge capacity.

[0054] The sulfur-modified aliphatic hydrocarbon oxide is obtained by heat-treating an aliphatic hydrocarbon oxide such as an aliphatic alcohol, an aliphatic aldehyde, an aliphatic ketone, an aliphatic epoxide, or a fatty acid with sulfur in a non-oxidizing atmosphere. Since the sulfur remaining after the heat treatment is a factor that deteriorates the cycle characteristics of a secondary battery, it is preferable to remove it from the sulfur-modified aliphatic hydrocarbon oxide by, for example, heating or washing with a solvent. The heat treatment is preferably performed in a temperature range of 300°C to 500°C. From the viewpoint of obtaining a large charge / discharge capacity, the sulfur content in the sulfur-modified aliphatic hydrocarbon oxide is preferably 40% by mass to 80% by mass, and more preferably 45% by mass to 75% by mass.

[0055] The polythienoacene compound is a compound having a sulfur-containing polythienoacene structure represented by the following general formula (1).

[0056] [ka]

[0057] The polythienoacene compound is obtained by heat-treating an aliphatic polymer compound having a linear structure such as polyethylene or a polymer compound having a thiophene structure such as polythiophene with sulfur in a non-oxidizing atmosphere. Since the sulfur remaining after the heat treatment is a factor that deteriorates the cycle characteristics of the secondary battery, it is preferable to remove it from the polythienoacene compound by, for example, heating or solvent washing. The heat treatment is preferably performed in a temperature range of 300°C to 600°C. From the viewpoint of obtaining a large charge / discharge capacity, the content of sulfur in the polythienoacene compound is preferably 25% by mass to 85% by mass, more preferably 30% by mass to 80% by mass.

[0058] The sulfur-modified polyamide compound is a sulfur-modified organic compound having a carbon skeleton derived from a polymer having an amide bond, and is specifically obtained by heat-treating an aminocarboxylic acid compound and sulfur in a non-oxidizing atmosphere, or by heat-treating a polyamine compound, a polycarboxylic acid compound and sulfur in a non-oxidizing atmosphere. Since the sulfur remaining after the heat treatment is a factor that reduces the cycle characteristics of a secondary battery, it is preferable to remove it from the sulfur-modified polyamide compound by, for example, heating or solvent washing. The heat treatment is preferably performed in a temperature range of 250°C to 600°C. The content of sulfur in the sulfur-modified polyamide compound is preferably 35% by mass to 75% by mass, more preferably 40% by mass to 70% by mass, from the viewpoint of obtaining a large charge / discharge capacity.

[0059] The polycarbon sulfide is represented by the general formula (CS x ) n(x is 0.5 to 2, and n is a number of 4 or more), and is obtained by, for example, heating a precursor in which a complex of an alkali metal sulfide such as sodium sulfide and sulfur is reacted with a halogenated unsaturated hydrocarbon such as hexachlorobutadiene. Since the sulfur remaining after the heat treatment is a factor that deteriorates the cycle characteristics of a secondary battery, it is preferable to remove it from the polycarbon sulfide by, for example, heating or solvent washing. The heat treatment is preferably performed in a temperature range of 300°C to 450°C. From the viewpoint of obtaining a large charge / discharge capacity, the content of sulfur in the polycarbon sulfide compound is preferably 60% by mass to 80% by mass, and more preferably 65% ​​by mass to 75% by mass.

[0060] The sulfur-carbon composite is a composite material containing sulfur in the pores of porous carbon or hollow carbon, capable of absorbing and releasing metal ions such as lithium, sodium, potassium, magnesium, aluminum, or calcium, and usable as an electrode active material for a secondary battery. The sulfur content in the sulfur-carbon composite material carrying sulfur in the pores of porous carbon or hollow carbon is preferably 25% by mass to 80% by mass, more preferably 30% by mass to 70% by mass, since if the content is too small, the charge / discharge capacity does not increase, and if the content is too large, the electronic conductivity decreases. A known method can be used to carry sulfur in the pores of porous carbon or hollow carbon. Examples of the porous carbon include carbon particles having a structure with a plurality of pores on the surface. Examples of the hollow carbon include carbon particles having a structure with a hollow structure inside the carbon particles and a plurality of pores on the surface.

[0061] The above sulfur includes liquid sulfur, rubber sulfur, inorganic sulfur (S8), Li2S n (n1≧1), organic sulfur compounds, sulfur polymers [(C2S x ) n2 , x=2 to 50, n2≧2]. In the present invention, from the viewpoint of producing an electrode having a large charge / discharge capacity, rubber-like sulfur, organic sulfur compounds, liquid sulfur, and inorganic sulfur are preferred, and inorganic sulfur is more preferred.

[0062] In the composition of the present invention, the shape of the active material other than the SPAN is not particularly limited, but examples thereof include spherical, polyhedral, fibrous, rod-like, plate-like, scaly, amorphous, etc. These may be hollow. The shape of the active material other than the SPAN is preferably spherical or polyhedral from the viewpoint of improving the coatability of the composition of the present invention.

[0063] When the composition of the present invention contains an active material other than the above SPAN, the content of SPAN is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 50 parts by mass or more, even more preferably 80 parts by mass or more, and most preferably 90 parts by mass or more, relative to 100 parts by mass of the total of SPAN and the active material other than SPAN. By setting the content of SPAN within the above range, the coatability of the composition of the present invention becomes better, and the decrease in charge / discharge capacity is less even when the electrode and battery obtained using the composition of the present invention are repeatedly charged and discharged.

[0064] In the composition of the present invention, the content of the active material containing SPAN, i.e., the total content of SPAN and the active material other than SPAN, is preferably 15 parts by mass or more, more preferably 20 parts by mass or more, even more preferably 25 parts by mass or more, and most preferably 30 parts by mass or more, relative to 100 parts by mass of the composition. The total content of SPAN and the active material other than SPAN is preferably 70 parts by mass or less, more preferably 68 parts by mass or less, even more preferably 65 parts by mass or less, even more preferably 50 parts by mass or less, and most preferably 40 parts by mass or less, relative to 100 parts by mass of the composition. By setting the total content of SPAN and the active material other than SPAN in the above-mentioned range, the effect of the present invention becomes remarkable.

[0065] A3-2. Binder The binder may be one having a function of holding the active material on the current collector or binding the active materials together. The composition of the present invention may be a known binder used in electrode materials. Specific examples of the binder include styrene-butadiene rubber, butadiene rubber, acrylonitrile-butadiene rubber, ethylene-propylene-diene rubber, styrene-isoprene rubber, fluororubber, polyethylene, polypropylene, polyacrylamide, polyamide, polyamideimide, polyimide, polyacrylonitrile, polyurethane, polyvinylidene fluoride, polytetrafluoroethylene, styrene-acrylic acid ester copolymer, ethylene-vinyl alcohol copolymer, polymethyl methacrylate, polyacrylate, polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone, polyvinyl ether, polyvinyl chloride, acrylic acid, polyacrylic acid, methylcellulose, carboxymethylcellulose, sodium carboxymethylcellulose, cellulose nanofiber, and starch. Among these, from the viewpoints of low environmental impact, excellent coating properties, and ease of suppressing leakage of the positive electrode active material from the positive electrode to the electrolyte, aqueous binders are preferred, styrene-butadiene rubber, sodium carboxymethylcellulose, and polyacrylic acid are more preferred, and styrene-butadiene rubber is even more preferred. Only one type of binder may be used, or two or more types may be used in combination.

[0066] The content of the binder in the composition of the present invention is preferably 0.2 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the composition. The content of the binder is preferably 18 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the composition. By setting the content of the binder within the above range, the decrease in charge / discharge capacity is less even when the electrode and battery obtained using the composition of the present invention are repeatedly charged and discharged.

[0067] The content of the binder in the composition of the present invention is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of SPAN. The content of the binder is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, and most preferably 5 parts by mass or less, relative to 100 parts by mass of SPAN. By setting the content of the binder within the above range, the decrease in charge / discharge capacity is less even when the electrode and battery obtained using the composition of the present invention are repeatedly charged and discharged.

[0068] A3-3.Conductive additives The conductive assistant may be one that improves the conductivity of the electrode. The composition of the present invention may contain a known conductive assistant used in electrode materials. Specific examples of the conductive assistant include natural graphite, artificial graphite, coal tar pitch, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, roller black, disc black, carbon nanotubes, vapor grown carbon fiber (VGCF), exfoliated graphite, graphene, fullerene, needle coke, and other carbon materials; metal powders such as aluminum powder, nickel powder, and titanium powder; conductive metal oxides such as zinc oxide and titanium oxide; and sulfides such as La2S3, Sm2S3, Ce2S3, and TiS2. Among these, from the viewpoint of obtaining an electrode having good conductivity, carbon materials are preferred, and carbon black, acetylene black, ketjen black, furnace black, carbon nanotubes, VGCF, and graphene are more preferred. These conductive assistants may be used alone or in combination of two or more. The conductive assistant may be mixed with SPAN.

[0069] The average particle diameter (D50) of the conductive assistant is preferably 0.0001 μm or more, more preferably 0.0005 μm or more, and even more preferably 0.001 μm or more. The average particle diameter (D50) of the conductive assistant is preferably 100 μm or less, more preferably 75 μm or less, and even more preferably 10 μm or less. By setting the average particle diameter (D50) of the conductive assistant within the above range, the coating property of the composition of the present invention becomes better, and an electrode having good conductivity can be easily obtained. In addition, in the electrode and battery obtained using the composition of the present invention, the decrease in charge and discharge capacity is less even when charging and discharging are repeated.

[0070] The content of the conductive assistant in the composition of the present invention is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.7 parts by mass or more, relative to 100 parts by mass of the composition. The content of the conductive assistant is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, even more preferably 20 parts by mass or less, even more preferably 10 parts by mass or less, and most preferably 5 parts by mass or less, relative to 100 parts by mass of the composition. By setting the content of the conductive assistant within the above range, the coating property of the composition of the present invention becomes better, and it becomes easier to obtain an electrode having good conductivity and a smooth surface. In addition, even if the electrode and battery obtained using the composition of the present invention are repeatedly charged and discharged, the decrease in charge and discharge capacity is less.

[0071] In addition, the content of the conductive assistant in the composition of the present invention is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of SPAN. The content of the conductive assistant is preferably 50 parts by mass or less, more preferably 30 parts by mass or less, and even more preferably 20 parts by mass or less, relative to 100 parts by mass of SPAN. By setting the content of the conductive assistant within the above range, the coating property of the composition of the present invention becomes better, and it becomes easier to obtain an electrode having good conductivity and a smooth surface. In addition, the charge / discharge capacity of the electrode and battery obtained using the composition of the present invention is less decreased even when the charge / discharge is repeated.

[0072] A3-4. Organic solvents The organic solvent may be one that adjusts the viscosity of the composition of the present invention or improves the coating property. The composition of the present invention may contain a known organic solvent used in electrode materials. As the organic solvent, one that is liquid at 25°C and atmospheric pressure and is other than the above-mentioned alcohol and water may be used. Specific examples of such organic solvents include, for example, propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, acetonitrile, propionitrile, tetrahydrofuran, 2-methyltetrahydrofuran, dioxane, 1,3-dioxolane, nitromethane, N-methylpyrrolidone, N,N-dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N,N-dimethylaminopropylamine, polyethylene oxide, tetrahydrofuran, dimethylsulfoxide, sulfolane, and γ-butyrolactone. These organic solvents may be used alone or in combination of two or more.

[0073] The content of the organic solvent in the composition of the present invention is not particularly limited, but from the viewpoint of making the effects of the present invention prominent, it is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 1 part by mass or less, relative to 100 parts by mass of the composition, and it is most preferably that the composition does not contain an organic solvent.

[0074] A3-5. Viscosity modifier The viscosity modifier may be one that adjusts the viscosity of the composition of the present invention. The composition of the present invention may contain a known viscosity modifier used in electrode materials. Specific examples of the viscosity modifier include the viscosity modifiers described in International Publication No. 2012 / 115096.

[0075] The content of the viscosity modifier in the composition of the present invention is not particularly limited, but is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and even more preferably 0.05 parts by mass or more, relative to 100 parts by mass of SPAN. The content of the viscosity modifier is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of SPAN. By setting the content of the viscosity modifier within the above range, the viscosity of the composition of the present invention becomes easy to handle.

[0076] A3-6. Reinforcement materials The reinforcing material may be one that improves the strength of the electrode or makes the electrode less likely to break. The composition of the present invention may contain a known reinforcing material used in electrode materials. Specific examples of the reinforcing material include various inorganic and organic spherical, plate-like, rod-like, or fibrous fillers such as fumed silica and fumed alumina.

[0077] The content of the reinforcing material in the composition of the present invention is not particularly limited, but is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of SPAN. The content of the reinforcing material is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of SPAN. By setting the content of the reinforcing material within the above range, the strength of the electrode obtained using the composition of the present invention is improved, and the electrode characteristics are excellent.

[0078] A3-7.Leveling agent The leveling agent may be one that improves the coating property of the composition of the present invention. The composition of the present invention may contain a known leveling agent used in batteries. Specific examples of the leveling agent include the leveling agents described in International Publication No. 2012 / 115096.

[0079] The content of the leveling agent in the composition of the present invention is not particularly limited, but is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, relative to 100 parts by mass of SPAN. The content of the leveling agent is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of SPAN. By setting the content of the leveling agent within the above range, the productivity and smoothness when manufacturing an electrode using the composition of the present invention may be improved, and the battery characteristics may be improved. In addition, the dispersibility of SPAN and other components contained in the composition of the present invention may be improved.

[0080] A3-8. Antioxidants The antioxidant may be one that suppresses the oxidation of the electrode material or improves the life of the electrode. The composition of the present invention may contain a known antioxidant used in electrode materials. Specific examples of the antioxidant include hindered phenol-based antioxidants and phosphite-based antioxidants described in International Publication No. 2019 / 172281.

[0081] The content of the antioxidant in the composition of the present invention is not particularly limited, but is preferably 0.01 parts by mass or more, more preferably 0.04 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the composition. The content of the antioxidant is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and even more preferably 1 part by mass or less, relative to 100 parts by mass of the composition. By setting the content of the antioxidant within the above range, the peel strength of the electrode obtained using the composition of the present invention can be improved, and the expansion of the electrode due to repeated charging and discharging in the battery can be suppressed.

[0082] A3-9. pH adjuster The pH adjuster may be one that adjusts the pH of the composition of the present invention. The composition of the present invention may contain a known pH adjuster used in electrode materials. Specific examples of the pH adjuster include the pH adjusters described in JP 2020-140957 A. The content of the pH adjuster is preferably added so that the pH of the composition of the present invention is within the range of 4.0 to 9.0, more preferably within the range of 4.5 to 8.5, and even more preferably within the range of 5.0 to 8.0. By setting the content of the pH adjuster within the above range, the dispersibility of the active material and conductive assistant contained in the composition of the present invention is improved, and the coatability is improved.

[0083] In the composition of the present invention, it is preferable that SPAN is dispersed. When dispersing SPAN and the above-mentioned other components, SPAN and the other components may be added to a mixed solvent of alcohol and water at the same time and dispersed, or SPAN and the other components may be added successively and dispersed. It is preferable to carry out a dispersion treatment every time SPAN and one of the other components are added to a mixed solvent of alcohol and water, since this makes it easier to disperse uniformly.

[0084] The method of the dispersion treatment is not particularly limited, but as an industrial method, for example, a normal ball mill, sand mill, bead mill, cyclone mill, zero mill, pigment disperser, crusher, ultrasonic disperser, homogenizer, homomixer, disperser, rotation-revolution mixer, planetary mixer, film mix, jet paste, etc. are usable. The dispersion treatment is usually preferably carried out within a range of room temperature to 80°C for a range of 5 minutes to several hours.

[0085] The method for storing the composition of the present invention is not particularly limited as long as it is a method that allows easy production of electrodes and batteries that maintain excellent coatability and exhibit little decrease in charge / discharge capacity even after repeated charging and discharging, and examples of the method include a method in which the composition is sealed to prevent moisture absorption and stored at a temperature of 20°C or lower.

[0086] B. Electrode Next, the electrode of the present invention will be described. The electrode of the present invention has an electrode active material layer (hereinafter, sometimes referred to as a SPAN-containing electrode active material layer) formed using the above-mentioned composition. The components constituting the composition are the same as those described in the section "A. Composition".

[0087] The thickness of the electrode of the present invention is preferably 1000 μm or less, more preferably 800 μm or less, and even more preferably 500 μm or less. The thickness of the electrode is preferably 20 μm or more, more preferably 30 μm or more, and even more preferably 40 μm or more. By setting the thickness of the electrode within the above range, an electrode having excellent charge / discharge capacity and cycle characteristics can be easily obtained. Furthermore, the decrease in charge / discharge capacity is less even when the electrode is repeatedly charged and discharged.

[0088] The electrode of the present invention can be used appropriately depending on the structure of the battery. For example, the electrode of the present invention can be used in batteries of various structures, such as a battery having a structure in which the electrode of the present invention and a counter electrode described later are laminated via a separator, a wound battery formed by further spirally winding a structure in which the electrode of the present invention and a counter electrode described later are laminated via a separator, and a stacked battery having a structure in which the electrode of the present invention and a counter electrode described later are alternately stacked in multiple layers. The shape of the electrode of the present invention is not particularly limited, and may be a rod-like, plate-like, disk-like, or other shape, or may be a multilayer structure including a SPAN-containing electrode active material layer.

[0089] B1.SPAN-containing electrode active material layer The SPAN-containing electrode active material layer used in the present invention is formed using the above-mentioned composition. The thickness of such a SPAN-containing electrode active material layer may be such that the charge / discharge capacity is unlikely to decrease even when the electrode and the battery are repeatedly charged and discharged, and may be, for example, 1 μm to 1,000 μm, preferably 5 μm to 500 μm, and more preferably 8 μm to 50 μm. By setting the thickness of the SPAN-containing electrode active material layer within the above-mentioned range, the charge / discharge capacity is less likely to decrease even when the electrode is repeatedly charged and discharged.

[0090] The electrode of the present invention may contain one SPAN-containing electrode active material layer, but may contain two or more layers. For example, when the electrode has a current collector as a component other than the SPAN-containing electrode active material layer, an embodiment in which two or more layers are contained may include an electrode in which SPAN-containing electrode active material layers are formed on both sides of the current collector.

[0091] An example of a method for forming such a SPAN-containing electrode active material layer is a method in which the above-mentioned composition is applied and then dried to remove the alcohol and water.

[0092] The method for applying the composition of the present invention is not particularly limited, and examples thereof include a die coater method, a comma coater method, a curtain coater method, a spray coater method, a gravure coater method, a flexo coater method, a knife coater method, a doctor blade method, a reverse roll method, a brush coating method, a dipping method, etc. Among these, the die coater method, the knife coater method, the doctor blade method, and the comma coater method are preferred from the viewpoint of being able to obtain a good surface condition of the coating layer in accordance with the viscosity and drying property of the composition.

[0093] The method for removing alcohol and water from the coating film of the composition is not particularly limited, and may be any method as long as the alcohol and water can be evaporated from the coating film of the composition. For example, a drying method using heating, a drying method using warm air, hot air, or low humidity air, a drying method using a difference in vapor pressure using vacuum drying, or a drying method using far infrared rays, infrared rays, or electron beams, etc. may be mentioned. These drying methods may be carried out in combination. The temperature when heating is generally about 50°C to 180°C, but the conditions such as temperature can be appropriately set depending on the coating amount of the above-mentioned composition used to form the coating film of the composition, the boiling point of the solvent used, the type of binder, etc.

[0094] The coating of the composition may be compressed or rolled after drying.

[0095] Although the SPAN-containing electrode active material layer is originally a material that does not contain lithium, it may be doped with lithium in advance since it has an irreversible capacity. Examples of methods for doping lithium into the SPAN-containing electrode active material layer include a method in which a half cell is assembled using metallic lithium as a counter electrode, and lithium is inserted by an electrolytic doping method in which lithium is electrochemically doped; a method in which a metallic lithium foil is attached to an electrode, and then left in an electrolyte, and lithium is inserted by a pasting doping method in which lithium is doped by utilizing the diffusion of lithium into the electrode; and a mechanical doping method in which the SPAN-containing electrode active material layer and lithium metal are mechanically collided to insert lithium, but the present invention is not limited to these methods.

[0096] B2. Current collector The electrode may have a current collector, if necessary, in addition to the SPAN-containing electrode active material layer. Examples of the material of the current collector include conductive materials such as titanium, titanium alloy, aluminum, aluminum alloy, copper, nickel, stainless steel, nickel-plated steel, and carbon. Examples of the shape of the current collector include foil, plate, net, three-dimensional net, foam, and nonwoven fabric, and the current collector may be porous or nonporous. In addition, these conductive materials may be surface-treated to improve adhesion and electrical properties. Among these conductive materials, aluminum is preferred from the viewpoint of conductivity and price, and aluminum foil is particularly preferred. When aluminum foil is used as the current collector, the thickness of the current collector is preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 5 μm or more. When aluminum foil is used as the current collector, the thickness of the current collector is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. By setting the thickness of the aluminum foil as the current collector to the above range, it becomes easier to ensure the thickness of the SPAN-containing electrode active material layer.

[0097] B3.Other configurations The electrode may have other components in addition to the SPAN-containing electrode active material layer and the current collector. Such other configurations include, for example, a coating layer that protects the SPAN-containing electrode active material layer. Methods for forming the coating layer include the above-mentioned layer containing a binder, water glass, etc.

[0098] C.Battery The battery of the present invention includes the above-mentioned electrode, counter electrode, and non-aqueous electrolyte. Each component of the battery of the present invention will be described below.

[0099] C1. Electrode The electrode used in the battery of the present invention has a SPAN-containing electrode active material layer, and the configuration of such an electrode is similar to that described in the section "B. Electrode."

[0100] C2. Opposite Examples of the counter electrode used in the battery of the present invention include metallic lithium, composite oxides containing lithium as an active material, silicon, silicon oxide, graphite, and electrodes containing carbon as an active material. In addition, other components such as binders, conductive assistants, organic solvents, viscosity adjusters, reinforcing materials, leveling agents, antioxidants, and pH adjusters may be included within the range that does not adversely affect the effects of the present invention. These components may be used alone or in combination of two or more types in any ratio. Examples of the other components include the same ones as those described in the section "A3. Other Components".

[0101] When metallic lithium is used as the counter electrode, the counter electrode can be made of metallic lithium and / or a lithium alloy. The counter electrode may be provided with a current collector made of a conductive material such as metallic lithium and / or a lithium alloy. In this case, an electrode active material layer containing metallic lithium may be formed. The electrode active material layer can be formed, for example, by a process such as attachment of metallic lithium foil, or electrodeposition or vapor deposition of metallic lithium.

[0102] The composite oxide containing lithium as the above active material is selected from the group consisting of a lithium transition metal composite oxide, a lithium transition metal silicate compound, and a lithium transition metal sulfate compound. The transition metal contained in these compounds is not particularly limited, but from the viewpoint of good charge and discharge stability of the lithium ion secondary battery, aluminum, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, magnesium, gallium, zirconium, niobium, boron, calcium, molybdenum, and tungsten are preferable, and from the viewpoint of remarkable effects of the present invention, aluminum, vanadium, titanium, chromium, manganese, iron, cobalt, nickel, and copper are more preferable, and aluminum, manganese, iron, cobalt, and nickel are even more preferable.

[0103] Examples of the lithium transition metal composite oxide include, for example, LiCoO2, LiNiO2, LiMnO2, the compound represented by the following general formula (2), and the compound represented by the following general formula (3). Li g Ni h Co i M1 j O2(2) Li (1+x) Mn (2-x-y) M1 y O4(3) In the formula, g, h, i, and j satisfy 0.9 ≦ g ≦ 1.2, 0.3 < h < 1, 0 ≦ i ≦ 0.5, 0 ≦ j ≦ 0.5, and h + i + j = 1, x satisfies 0 ≦ x < 0.5, and y satisfies 0 ≦ y < 0.5. M1 is at least one selected from the group consisting of aluminum, titanium, vanadium, chromium, manganese, iron, copper, zinc, magnesium, gallium, zirconium, niobium, boron, calcium, molybdenum, and tungsten.

[0104] Specific examples of the compound represented by the general formula (2) or the compound represented by the general formula (3) include, for example, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1O2, LiNi 0.5 Mn 1.5 O4, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.80 Co 0.17 Al 0.03 O2, LiNi 0.90 Co 0.05 Al 0.05 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiMn 1.8 Al 0.2 O4, Li 1.1 Mn 1.8 Mg 0.1 O4, Li 1.1 Mn 1.85 Al 0.05 O4, Li2MnO3-LiMO2 (M = cobalt, nickel, manganese), etc.

[0105] As the lithium transition metal composite oxide, for example, LiCoO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05 O2 is preferred.

[0106] An example of the lithium transition metal phosphate compound is a compound represented by the following general formula (4). Li k M2 m (PO4)n F p (4) In the formula, k satisfies 0 < k ≤ 3, m satisfies 0.5 ≤ m ≤ 2, n satisfies 1 ≤ n ≤ 3, and p satisfies 0 ≤ p ≤ 1. M2 is at least one selected from the group consisting of iron, cobalt, nickel, manganese, copper, titanium, tungsten, molybdenum, chromium, vanadium, and vanadium(II) monoxide. Since it has good charge-discharge stability, at least one selected from the group consisting of iron, cobalt, nickel, manganese, copper, vanadium, and vanadium(II) monoxide is preferred. Also, a part of M2 may be substituted with one or more other metals such as aluminum, zinc, magnesium, zirconium, gallium, and niobium.

[0107] Specific examples of the above lithium transition metal phosphate compound include, for example, LiFePO4, LiMn X Fe 1-X PO4, LiCuPO4, LiNiPO4, LiCoPO4, LiMnPO4, LiVOPO4, Li2FePO4, Li2NiPO4, Li2CoPO4, Li2MnPO4, Li2NiPO4F, Li2CoPO4F, Li2MnPO4F, Li2FePO4F, Li3V2(PO4)3, LiMn 7 / 8 Fe 1 / 8 PO4, LiMn 2 / 3 Fe 1 / 3 PO4, LiFe 0.9 Mn 0.1 PO4, LiFe 0.2 Mn 0.8 PO4, LiFe 0.15 Mn 0.75 Mg 0.1 PO4, LiFe 0.19 Mn 0.75 Zr 0.03 PO4, etc.

[0108] As the above lithium transition metal phosphate compound, since it has good charge-discharge stability, LiFePO4, LiCuPO4, LiNiPO4, LiCoPO4, LiMnPO4, and LiVOPO4 are preferred, and LiFePO4, LiNiPO4, LiCoPO4, and LiMnPO4 are more preferred.

[0109] The counter electrode active material is preferably pulverized, granulated, or the like to a desired particle size, and is preferably further classified. Methods for pulverization and classification include the same methods for pulverization and granulation as those described in the section "A1. Sulfur-modified polyacrylonitrile."

[0110] The average particle size (D50) of the counter electrode active material is preferably 0.1 μm to 50 μm, more preferably 1 μm to 50 μm, and even more preferably 1 μm to 30 μm. By setting the average particle size (D50) of the counter electrode active material within the above-mentioned numerical range, the handleability of the active material is improved, and the charge / discharge stability of the battery when the counter electrode active material is used as a battery material is improved.

[0111] The counter electrode can be manufactured by the same method as the electrode manufacturing method described in the section "B. Electrode". For example, a method of manufacturing a counter electrode includes dispersing a composition containing an active material of the counter electrode, a binder, a conductive assistant, and optionally other components described in the section "A3. Other components", and a mixed solvent of alcohol and water or an organic solvent on a current collector so that the active material of the counter electrode is dispersed, and immediately applying the composition to the current collector and drying to remove the alcohol and water or the organic solvent to form a layer containing the active material of the counter electrode. The alcohol can be the same as that described in the section "A2. Alcohol and water". The conductive assistant can be the same as that described in the section "A3-3. Conductive assistant", and the organic solvent can be the same as that described in the section "A3-4. Organic solvent".

[0112] The binder used in the counter electrode can be the same as that described in the section "A3-2. Binder". From the viewpoint of improving charge / discharge stability, however, polyvinylidene fluoride, polyimide, polyacrylonitrile, polytetrafluoroethylene, polyacrylic acid, and sodium carboxymethylcellulose are preferred.

[0113] The method for dispersing the counter electrode composition, the method for applying the counter electrode composition onto a current collector, and the method for removing the alcohol and water or the organic solvent from the counter electrode composition can be performed by the same methods as those described in the section "B. Electrode."

[0114] C3.Nonaqueous electrolyte Examples of non-aqueous electrolytes that can be used in the battery of the present invention include liquid non-aqueous electrolytes obtained by dissolving an electrolyte in an organic solvent, polymer gel non-aqueous electrolytes obtained by dissolving or dispersing an electrolyte using a polymer gel obtained by dissolving a polymer compound in an organic solvent as a solvent or dispersion medium, polymer non-aqueous electrolytes obtained by dispersing an electrolyte without using a solvent using a polymer as a dispersion medium (in this specification, an electrolyte obtained by dispersing an electrolyte without using a solvent and using a polymer as a dispersion medium is also referred to as a "polymer electrolyte"), complex hydride-based solid electrolytes, inorganic solid electrolytes, and the like.

[0115] C3-1. Electrolyte The electrolyte used for the non-aqueous electrolyte is not particularly limited as long as it is a known electrolyte used for non-aqueous electrolytes in non-aqueous electrolyte secondary batteries, and examples of the electrolyte include lithium salts, sodium salts, potassium salts, calcium salts, and magnesium salts.

[0116] Specific examples of the lithium salt include LiPF6, LiBF4, LiAsF6, LiCF3SO3, LiCF3CO2, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiC(CF3SO2)3, LiB(CF3SO3)4, LiB(C2O4)2, LiBF2(C2O4), LiSbF6, LiSiF5, LiSCN, LiClO4, LiCl, LiF, LiBr, LiI, LiAlF4, LiAlCl4, LiPO2F2, and derivatives thereof.

[0117] Specific examples of the sodium salts include NaPF6, NaBF4, NaAsF6, NaCF3SO3, NaCF3CO2, NaN(CF3SO2)2, NaN(C2F5SO2)2, NaN(SO2F)2, NaC(CF3SO2)3, NaB(CF3SO3)4, NaB(C2O4)2, NaBF2(C2O4), NaSbF6, NaSiF5, NaSCN, NaClO4, NaCl, NaF, NaBr, NaI, NaAlF4, NaAlCl4, NaPO2F2, and derivatives thereof.

[0118] Specific examples of the potassium salts include KPF6, KBF4, KAsF6, KCF3SO3, KCF3CO2, KN(CF3SO2)2, KN(C2F5SO2)2, KN(SO2F)2, KC(CF3SO2)3, KB(CF3SO3)4, KB(C2O4)2, KBF2(C2O4), KSbF6, KSiF5, KSCN, KClO4, KCl, KF, KBr, KI, KAlF4, KAlCl4, KPO2F2, and derivatives thereof.

[0119] Specific examples of the calcium salt include Ca(PF6)2, Ca(BF4)2, Ca[FSI]2, Ca[TFSI]2, Ca[f3C]2, Ca[BOB]2, Ca(ClO4)2, Ca[BF3(CF3)]2, Ca[BF3(C2F5)]2, Ca[BF3(C3F7)]2, Ca[BF3(C4F9)]2, Ca[C(SO2CF3)3]2, Ca(CF3SO2O)2, Ca(CF3COO)2, and Ca(RCOO)2 (R is an alkyl group having 1 to 4 carbon atoms, a phenyl group, or a naphthyl group), and derivatives thereof.

[0120] Specific examples of the magnesium salt include Mg(PF6)2, Mg(BF4)2, Mg[FSI]2, Mg[TFSI]2, Mg[f3C]2, Mg[BOB]2, Na(ClO4)2, Mg[BF3(CF3)]2, Mg[BF3(C2F5)]2, Mg[BF3(C3F7)]2, Mg[BF3(C4F9)]2, Mg[C(SO2CF3)3]2, Mg(CF3SO3)2, Mg(CF3COO)2, and Mg(RCOO)2 (R is an alkyl group having 1 to 4 carbon atoms, a phenyl group, or a naphthyl group), and derivatives thereof.

[0121] In the present invention, the electrolyte is preferably a lithium salt or a sodium salt, and more preferably a lithium salt.

[0122] As the lithium salt used in the liquid nonaqueous electrolyte and the polymer gel nonaqueous electrolyte, from the viewpoint of prominent effects of the present invention, one or more selected from the group consisting of LiPF6, LiBF4, LiClO4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiPO2F2, LiC(CF3SO2)3, derivatives of LiCF3SO3, and derivatives of LiC(CF3SO2)3 are preferred.

[0123] As the lithium salt used in the polymer electrolyte (or a polymer electrolyte obtained by dispersing a lithium salt without using a solvent), from the viewpoint of making the effects of the present invention prominent, one or more selected from the group consisting of LiPF6, LiBF4, LiClO4, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(SO2F)2, LiC(CF3SO2)3, LiB(CF3SO3)4 and LiB(C2O4)2 are preferred.

[0124] The concentration of the lithium salt in the non-aqueous electrolyte is preferably 0.5 mol / L or more, more preferably 0.6 mol / L or less, and even more preferably 0.8 mol / L or less. The concentration of the lithium salt in the non-aqueous electrolyte is preferably 7 mol / L or less, more preferably 3 mol / L or less, and even more preferably 1.8 mol / L or less. By setting the concentration of the lithium salt in the non-aqueous electrolyte within the above range, a sufficient current density is obtained, and the stability of the non-aqueous electrolyte is improved.

[0125] C3-2.Liquid non-aqueous electrolyte The liquid nonaqueous electrolyte contains a lithium salt and an organic solvent. The organic solvent used in such a liquid nonaqueous electrolyte preferably contains at least one compound selected from cyclic carbonate compounds. Examples of the cyclic carbonate compound include saturated cyclic carbonate compounds such as ethylene carbonate, 1,2-propylene carbonate, 1,3-propylene carbonate, 1,2-butylene carbonate, 1,3-butylene carbonate, and 1,1-dimethylethylene carbonate, and unsaturated cyclic carbonate compounds such as vinylene carbonate, vinylethylene carbonate, propylidene carbonate, ethylene ethylidene carbonate, and ethylene isopropylidene carbonate. These cyclic carbonate compounds may have some of the hydrogen atoms substituted with fluorine atoms.

[0126] When the non-aqueous electrolyte contains a cyclic carbonate compound, the viscosity is reduced and the ion conductivity is improved, so it is preferable that the organic solvent further contains a chain carbonate compound. Examples of the chain carbonate compound include saturated chain carbonate compounds such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and dipropyl carbonate, and unsaturated chain carbonate compounds such as dipropargyl carbonate, propargyl methyl carbonate, ethyl propargyl carbonate, bis(1-methylpropargyl) carbonate, and bis(1-dimethylpropargyl) carbonate. In these chain carbonate compounds, a part of the hydrogen atoms may be replaced by fluorine atoms.

[0127] In terms of the performance and storage stability of the lithium ion secondary battery, the organic solvent of the liquid nonaqueous electrolyte is preferably propylene carbonate, a mixed solvent of ethylene carbonate and dimethyl carbonate, a mixed solvent of ethylene carbonate and ethyl methyl carbonate, a mixed solvent of ethylene carbonate and diethyl carbonate, a mixed solvent of propylene carbonate and dimethyl carbonate, a mixed solvent of propylene carbonate and diethyl carbonate, or a mixed solvent of propylene carbonate, ethylene carbonate and ethyl methyl carbonate, and more preferably propylene carbonate, a mixed solvent of ethylene carbonate and ethyl methyl carbonate, a mixed solvent of ethylene carbonate and diethyl carbonate, a mixed solvent of propylene carbonate and diethyl carbonate, or a mixed solvent of propylene carbonate, ethylene carbonate and ethyl methyl carbonate.

[0128] When the organic solvent contained in the liquid non-aqueous electrolyte contains a chain carbonate compound, the content of the chain carbonate compound is preferably 10 parts by volume or more, more preferably 30 parts by volume or more, and even more preferably 50 parts by volume or more, relative to 100 parts by volume of the cyclic carbonate compound. The content of the chain carbonate compound is preferably 1,000 parts by volume or less, more preferably 300 parts by volume or less, and even more preferably 150 parts by volume or less, relative to 100 parts by volume of the cyclic carbonate compound. By setting the content of the chain carbonate compound within the above range, the performance of the lithium ion secondary battery is improved, and the charge / discharge stability at high temperatures is improved.

[0129] The organic solvent contained in the liquid non-aqueous electrolyte may contain, in addition to the organic solvents described above, organic solvents that are usually used in non-aqueous electrolytes for lithium ion secondary batteries.Specific examples of the organic solvent include saturated cyclic ester compounds, sulfoxide compounds, sulfone compounds, amide compounds, chain ether compounds, cyclic ether compounds, and saturated chain ester compounds.These organic solvents may be used alone or in combination of two or more.

[0130] Examples of the saturated cyclic ester compound include γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-hexanolactone, and δ-octanolactone.

[0131] Examples of the sulfoxide compound include dimethyl sulfoxide, diethyl sulfoxide, dipropyl sulfoxide, diphenyl sulfoxide, and thiophene.

[0132] Examples of sulfone compounds include dimethyl sulfone, diethyl sulfone, dipropyl sulfone, diphenyl sulfone, sulfolane (also called tetramethylene sulfone), 3-methyl sulfolane, 3,4-dimethyl sulfolane, 3,4-diphenylmethyl sulfolane, sulfolene, 3-methyl sulfolene, 3-ethyl sulfolene, 3-bromomethyl sulfolene, etc. Among these, sulfolane and tetramethyl sulfolane are preferred.

[0133] Examples of the amide compound include N-methylpyrrolidone, dimethylformamide, and dimethylacetamide.

[0134] Examples of chain ether compounds and cyclic ether compounds include dimethoxyethane, ethoxymethoxyethane, diethoxyethane, tetrahydrofuran, dioxolane, dioxane, 1,2-bis(methoxycarbonyloxy)ethane, 1,2-bis(ethoxycarbonyloxy)ethane, 1,2-bis(ethoxycarbonyloxy)propane, ethylene glycol bis(trifluoroethyl)ether, propylene glycol bis(trifluoroethyl)ether, ethylene glycol bis(trifluoromethyl)ether, and diethylene glycol bis(trifluoroethyl)ether. Of these, dioxolane is preferred.

[0135] The saturated chain ester compound is preferably a monoester compound or a diester compound having 2 to 8 carbon atoms in the molecule in total. Specific examples of the compound include methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl propionate, ethyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethylacetate, ethyl trimethylethylacetate, methyl malonate, ethyl malonate, methyl succinate, ethyl succinate, methyl 3-methoxypropionate, ethyl 3-methoxypropionate, ethylene glycol diacetyl, and propylene glycol diacetyl. Of these, methyl formate, ethyl formate, methyl acetate, ethyl acetate, propyl acetate, isobutyl acetate, butyl acetate, methyl propionate, and ethyl propionate are preferred.

[0136] Other organic solvents that can be used include, for example, acetonitrile, propionitrile, nitromethane, and derivatives thereof, and various ionic liquids.

[0137] C3-3. Polymer gel-type non-aqueous electrolyte Examples of polymers that can be used as the polymer gel include polyethylene oxide, polypropylene oxide, polyvinyl chloride, polyacrylonitrile, polymethyl methacrylate, polyethylene, polyvinylidene fluoride, polyhexafluoropropylene, polystyrene sulfonic acid, etc. There are no particular limitations on the organic solvent that dissolves the polymer to gel, the blending ratio of the lithium salt and the polymer gel, and the method for producing the polymer gel, and any organic solvent, lithium salt, and production method known in the art can be used.

[0138] C3-4.Polymer nonaqueous electrolyte Examples of polymers that can be used as the polymer nonaqueous electrolyte obtained by dispersing a lithium salt using a polymer as a dispersion medium without using a solvent include polyethylene oxide, polypropylene oxide, and polystyrene sulfonic acid. There are no particular limitations on the blending ratio of the lithium salt and the polymer in the polymer nonaqueous electrolyte, and on the method for producing the polymer nonaqueous electrolyte, and any blending ratio and production method known in the art can be used.

[0139] C3-5. Complex hydride solid electrolytes Complex hydride solid electrolytes include Li(CB9H 10 ), Li(CB 11 H 12 ), Li2(B 12 H 12 ), Li(BH4), 3(LiBH4)-LiI, Li(NH2), Li(AlH4), Li3(AlH6), 3(LiBH4)-Li(NH2), Li(BH4)-Li(NH2), 0.7Li(CB9H 10 )-0.3Li(CB 11 H 12 ), Li(BH4)-3KI, Li(BH4)-P2I4, ​​Li(BH4)-P2S5, Li2(NH2), Li(BH4)-GdCl3, Li(BH4)-NaI, Li(BH4)-3Li(NH2), etc.

[0140] C3-6. Inorganic solid electrolyte As an inorganic solid electrolyte, for example, Li 1+x’ A x’ B 2-x’ (PO4)3 (A = Al, Ge, Sn, Hf, Zr, Sc or Y, B = Ti, Ge or Zn, 0 <x ’ <1), LiMPO4 (M = Mn, Fe, Co or Ni), Li3PO4, Li 2.9 PO 3.3 N 0.46 Phosphate-based materials such as Li3XO4 (X=As or V), Li 3+x” A x” B 1-x” O4 (A=Si, Ge or Ti, B=P, As or V, 0 <x ” <0.6), Li 4+y’ A y’ S 1-y’ O4 (A = B, Al, Ga, Cr or Fe, 0 <y’<0.4)、Li 4-3y” Al y” SiO4(0 <y”<0.06)、Li4-2z’ Zn z’ GeO4(0 < z’ < 0.25), LiAlO2, Li2BO4, Li4XO4 (X = Si, Ge or Ti), lithium titanates (LiTiO2, LiTi2O4, Li4TiO4, Li2TiO3, Li2Ti3O7, Li4Ti5O 12 ) and other lithium composite oxides; compounds containing lithium and halogen such as LiBr, LiF, LiCl, LiPF6, LiBF4; compounds containing lithium and nitrogen such as LiPON, LiN(SO2CF3)2, LiN(SO2C2F5)2, Li3N, LiN(SO2C3F7)2; La 0.55 Li 0.35 TiO3, Li 0.34 La 0.51 TiO 2.94 and other crystals having a perovskite structure with lithium ion conductivity; Li7La3Zr2O 12 and other crystals having a garnet structure; crystals having an argyrodite structure such as Li6PS5Cl; glasses such as 50Li4SiO4·50Li3BO3, 90Li3BO3·10Li2SO4; Li 10 GeP2S 12 、Li 3.25 Ge 0.25 P 0.75 S4, Li 9.6 P3S 12 、Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 and other lithium-phosphorus sulfide-based crystals, lithium-phosphorus sulfide-based glasses such as 30Li2S·26B2S3·44LiI, 63Li2S·36SiS2·1Li3PO4, 57Li2S·38SiS2·5Li4SiO4, 70Li2S·30P2S5, 50Li2S·50GeS2; Li7P3S 11 、Li 3.25 P 0.95 S4, Li 10 GeP2S 12 and other glass-ceramics, etc. can be mentioned.

[0141] In the lithium ion secondary battery of the present invention, the form of the non-aqueous electrolyte is not particularly limited, but it is preferable to use a liquid non-aqueous electrolyte because the production process is simple.

[0142] The non-aqueous electrolyte may further contain known electrolyte additives such as an electrode film forming agent, an antioxidant, a flame retardant, an overcharge inhibitor, etc., for improving battery life and safety. When an electrolyte additive is used, the concentration is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, and even more preferably 0.1% by mass or more, based on the non-aqueous electrolyte. When an electrolyte additive is used, the concentration is preferably 10% by mass or less, more preferably 7% by mass or less, and even more preferably 5% by mass, based on the non-aqueous electrolyte. By setting the concentration of the electrolyte additive within the above range, the addition effect can be sufficiently obtained, and there is little adverse effect on the characteristics of the lithium ion secondary battery.

[0143] C4. Other battery materials In addition to the electrodes, counter electrode, and non-aqueous electrolyte, the battery of the present invention may contain other battery materials as necessary, such as a separator and an external packaging.

[0144] C4-1.Separator The separator is a battery material used to provide a separation between the electrode of the present invention and the counter electrode. When a liquid non-aqueous electrolyte is used as the non-aqueous electrolyte, it is preferable to interpose a separator between the working electrode and the counter electrode. The separator can be selected from polymer films, nonwoven fabrics, and glass filters that are usually used in lithium ion secondary batteries without any particular limitation. Specific examples of polymer films include films made of polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene chloride, polyacrylonitrile, polyacrylamide, polytetrafluoroethylene, polysulfone, polyethersulfone, polycarbonate, polyamide, polyimide, polyethers such as polyethylene oxide and polypropylene oxide, various celluloses such as carboxymethyl cellulose and hydroxypropyl cellulose, polymer compounds mainly composed of poly(meth)acrylic acid and various esters thereof, derivatives thereof, copolymers or mixtures thereof, etc., and these polymer films may be coated with ceramic materials such as alumina and silica, magnesium oxide, aramid resin, and polyvinylidene fluoride. These polymer films may be used alone, or these films may be stacked together to form a multilayer film. Furthermore, various additives may be used in these polymer films, and the type and content of the additives are not particularly limited. Among these polymer films, films selected from polyethylene, polypropylene, polyvinylidene fluoride, and polysulfone are preferably used.

[0145] These polymer films are used in a microporous state so that the nonaqueous electrolyte can penetrate and ions can easily pass through. Methods for making the polymer film microporous include the "phase separation method" in which a solution of a polymer compound and a solvent is subjected to microphase separation to form a film, and the solvent is extracted and removed to make the film porous, and the "stretching method" in which a molten polymer compound is extruded at a high draft to form a film, and then heat-treated to align the crystals in one direction, and then stretched to form gaps between the crystals to make the film porous. The method is appropriately selected depending on the polymer film to be used.

[0146] When a polymer gel electrolyte, a polymer electrolyte (or a polymer electrolyte obtained by dispersing a lithium salt without using a solvent), a complex hydride-based solid electrolyte, or an inorganic solid electrolyte is used as the non-aqueous electrolyte, a separator may not be included.

[0147] C4-2.External packaging The shape of the battery of the present invention is not particularly limited, and can be a coin-type battery, a cylindrical battery, a square battery, a laminated battery, or other battery of various shapes, and a metal container or a laminate film can be used as the external packaging member. The thickness of the external packaging member is usually 0.5 mm or less, and preferably 0.3 mm or less. The shape of the external packaging member can be a flat (thin), square, cylindrical, coin, button, or other shape.

[0148] Examples of metal containers include those made of stainless steel, aluminum, aluminum alloys, etc. The aluminum alloy is preferably an alloy containing elements such as magnesium, zinc, silicon, etc. In aluminum or aluminum alloys, the content of transition metals such as iron, copper, nickel, chromium, etc. is preferably 1% or less. By setting the content within the above range, it is possible to dramatically improve long-term reliability and heat dissipation properties in high-temperature environments.

[0149] The laminate film may be a multi-layer film having a metal layer between resin films. The metal layer is preferably an aluminum foil or an aluminum alloy foil for weight reduction. The resin film may be made of a polymer material such as polypropylene, polyethylene, nylon, or polyethylene terephthalate. The laminate film may be sealed by heat fusion to form an exterior member.

[0150] C5. Battery Uses Examples of applications of the battery of the present invention include power sources for portable electronic devices such as smartphones, portable personal computers, and handy video cameras, driving power sources for hybrid automobiles or electric automobiles, and storage batteries for renewable energy.

[0151] FIG. 1 shows an example of a coin-type battery (lithium ion secondary battery) of the present invention, FIGS. 2 and 3 show examples of a cylindrical battery, and FIGS. 4 to 6 show examples of a laminated battery.

[0152] In the coin-type battery 10 shown in FIG. 1, 1 is a SPAN-containing electrode active material layer, 1a is a positive electrode current collector, 2 is a negative electrode active material layer capable of absorbing and releasing lithium ions released from the positive electrode, 2a is a negative electrode current collector, 3 is a nonaqueous electrolyte, 4 is a stainless steel positive electrode case for external packaging, 5 is a stainless steel negative electrode case for external packaging, 6 is a polypropylene gasket, and 7 is a polyethylene separator. In this example, the positive electrode includes a SPAN-containing electrode active material layer 1 and a positive electrode current collector 1a, and the negative electrode, which is the counter electrode, includes a negative electrode active material layer 2 and a negative electrode current collector 2a.

[0153] In a cylindrical battery (lithium ion secondary battery) 10′ shown in FIGS. 2 and 3 , 11 is a negative electrode active material layer, 12 is a negative electrode current collector, 13 is a SPAN-containing electrode active material layer, 14 is a positive electrode current collector, 15 is a nonaqueous electrolyte, 16 is a separator, 17 is a positive electrode terminal, 18 is a negative electrode terminal, 19 is a negative electrode plate, 20 is a negative electrode lead, 21 is a positive electrode plate, 22 is a positive electrode lead, 23 is a case, 24 is an insulating plate, 25 is a gasket, 26 is a safety valve, and 27 is a PTC element. In this example, the positive electrode includes a SPAN-containing electrode active material layer 1 and a positive electrode current collector 1a, and the negative electrode, which is the counter electrode, includes a negative electrode active material layer 2 and a negative electrode current collector 2a.

[0154] 4 is an exploded perspective view showing a schematic diagram of an electrode group 29 of a laminated type battery (lithium ion secondary battery) 28. In the embodiment described later, a laminated type lithium ion secondary battery will be used for explanation, but the present invention is not limited thereto. The electrode group 29 has a structure in which, for example, a sheet-shaped negative electrode active material layer 11, a sheet-shaped SPAN-containing electrode active material layer 13, and a sheet-shaped separator 16 separating the negative electrode 11 and the positive electrode 13 are alternately laminated. 17 is a positive electrode terminal, and 18 is a negative electrode terminal. In this example, the electrode serving as the positive electrode is the SPAN-containing electrode active material layer 13, and the negative electrode serving as the counter electrode is the negative electrode active material layer 2.

[0155] Fig. 5 is an exploded perspective view that typically shows a laminated battery (lithium ion secondary battery) 28, and Fig. 6 is an external plan view that typically shows a laminated battery (lithium ion secondary battery) 28. Reference numeral 17 denotes a positive electrode terminal, 18 denotes a negative electrode terminal, 29 denotes an electrode group, 30 denotes a case-side laminate film, and 31 denotes a lid-side laminate film.

[0156] D. Electrode active material Next, the electrode active material of the present invention will be described. The electrode active material of the present invention is an electrode active material containing sulfur-modified polyacrylonitrile, which is added to a composition containing alcohol and water, and the composition is characterized in that the alcohol content is 0.1% by mass to 50% by mass with respect to the total of the alcohol and water. According to the present invention, the electrode active material of the present invention is used as an additive to a composition that contains SPAN and further contains alcohol and water in a predetermined ratio, and therefore the electrode active material of the present invention has better coatability and makes it easy to prepare a composition that can be used to manufacture electrodes and batteries that exhibit little decrease in charge-discharge capacity even after repeated charge-discharge processes.

[0157] The electrode active material of the present invention contains SPAN. Hereinafter, each component of such an electrode active material will be described in detail.

[0158] D1. Sulfur-modified polyacrylonitrile The SPAN can be the same as that described in the section "A1. Sulfur-modified polyacrylonitrile" in "A. Composition" above, and therefore a description thereof will be omitted here.

[0159] The content of the SPAN is not particularly limited as long as it makes it easy to prepare a composition capable of producing an electrode and a battery having better coatability and exhibiting less decrease in charge / discharge capacity even after repeated charging and discharging. For example, the electrode active material may contain only SPAN, or SPAN may be contained as a part of the electrode active material. In the present invention, the content of the SPAN is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 50 parts by mass or more, even more preferably 70 parts by mass or more, and most preferably 80 parts by mass or more, relative to 100 parts by mass of the electrode active material, because this makes it easier to prepare a composition capable of producing an electrode and a battery having better coatability and less decrease in charge / discharge capacity even after repeated charge / discharge. When the electrode active material contains an active material other than SPAN, the content of SPAN is preferably 10 parts by mass or more, more preferably 30 parts by mass or more, even more preferably 50 parts by mass or more, even more preferably 80 parts by mass or more, and most preferably 90 parts by mass or more, relative to 100 parts by mass in total of SPAN and the active material other than SPAN. This is because it is easy to prepare a composition capable of producing an electrode and a battery having better coatability and less decrease in charge / discharge capacity even after repeated charge / discharge.

[0160] D2. Other ingredients The electrode active material contains SPAN, but may contain other components as necessary. Such other components may be the same as those described in the section "A3. Other Components" in "A. Composition" above. The total content of these other components can be 50 parts by mass or less in 100 parts by mass of the electrode active material, preferably 1 part by mass or more and 30 parts by mass or less, more preferably 2 parts by mass or more and 20 parts by mass or less, and even more preferably 3 parts by mass or more and 10 parts by mass or less, because it is easy to prepare a composition capable of producing an electrode and a battery having better coatability and less decrease in charge / discharge capacity even after repeated charge / discharge.

[0161] D3. Electrode active material The electrode active material can be prepared by a known method. When the electrode active material is composed of only SPAN, the preparation method can be the same as the preparation method of SPAN. When the electrode active material contains SPAN and the other components, the method of mixing SPAN and the other components by a known method can be used.

[0162] The method for storing the electrode active material is not particularly limited as long as it is a method that can easily prepare a composition that can be used to manufacture electrodes and batteries that have better coatability and exhibit less decrease in charge / discharge capacity even after repeated charging and discharging. For example, the method may include a method in which the material is sealed to prevent moisture absorption and stored at a temperature of 20°C or lower.

[0163] Although the embodiment of the present invention has been described above, the present invention is not limited to the above-mentioned embodiment. The present invention can be embodied in various forms including modifications and improvements that can be made by those skilled in the art without departing from the gist of the present invention. EXAMPLES

[0164] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.

[0165] Raw material PAN mixture: 10 parts by mass of polyacrylonitrile powder (manufactured by Sigma-Aldrich, average particle size 200 μm) and 30 parts by mass of sulfur powder (manufactured by Sigma-Aldrich, average particle size 200 μm) were mixed in a mortar to obtain the raw material of sulfur-modified polyacrylonitrile in Production Examples 1 to 4.

[0166] [Production Example 1] Production of SPAN (A-1) Sulfur-modified polyacrylonitrile was produced by a method according to the manufacturing example of JP 2013-054957 A. That is, 20 g of the raw material PAN mixture was placed in a bottomed cylindrical glass tube with an outer diameter of 45 mm and a length of 120 mm, and then a silicone plug having a gas inlet tube and a gas outlet tube was attached to the opening of the glass tube. After replacing the air inside the glass tube with nitrogen, the lower part of the glass tube was placed in a crucible-type electric furnace, and heated at 400 ° C. for 1.5 hours while introducing nitrogen from the gas inlet tube to remove the generated hydrogen sulfide. The sulfur vapor was condensed at the upper part or the lid of the glass tube and refluxed. The obtained intermediate product was placed in a glass tube oven at 300 ° C., reduced pressure, and heated at 20 hPa for 3 hours to remove sulfur. The obtained sulfur-modified product was pulverized using a ball mill for 30 hours, and then classified with a sieve to obtain sulfur-modified polyacrylonitrile SPAN (A-1).

[0167] [Production Example 2] Production of SPAN (A-2) The same operation as in Production Example 1 was carried out to obtain a sulfur-modified polyacrylonitrile SPAN (A-2), except that the conditions for removing sulfur from the obtained intermediate product in Production Example 1 were changed from the conditions of heating at 300°C under reduced pressure and 20 hPa for 3 hours to the conditions of heating at 260°C under normal pressure and nitrogen flow for 20 hours.

[0168] [Production Example 3] Production of SPAN (A-3) The same operation as in Production Example 1 was carried out except that the conditions for pulverizing the obtained sulfur-modified product were changed from 30 hours of pulverization using a ball mill to 60 hours of pulverization using a ball mill in Production Example 1, thereby obtaining a sulfur-modified polyacrylonitrile SPAN (A-3).

[0169] [Production Example 4] Production of SPAN (A-4) In Production Example 2, the conditions for pulverizing the obtained sulfur-modified product were changed from 30 hours of pulverization using a ball mill to 60 hours of pulverization using a ball mill, but the same operation as in Production Example 2 was performed to obtain sulfur-modified polyacrylonitrile SPAN (A-4).

[0170] The sulfur content and average particle size of the SPAN obtained in Production Examples 1 to 4 were measured by the following methods. The results are shown in Table 1 below.

[0171] [Sulfur content] The sulfur content was calculated based on the analysis results using a CHN analyzer (model: varioMICROcube, manufactured by Elementar Analysensysteme GmbH) capable of analyzing sulfur and oxygen.

[0172] [Average particle size] Using water as a dispersion medium, the volumetric diameter was measured using a laser diffraction / scattering type particle size distribution measuring device (manufactured by Horiba, Ltd., model: LA-950V2), and the average particle size was calculated.

[0173] [Table 1]

[0174] [Example 1-1] Preparation of Composition A-1 90 parts by mass of SPAN (A-1) as an active material, 5 parts by mass of acetylene black (manufactured by Denka Co., Ltd.) as a conductive assistant, 3.0 parts by mass (solid content) of styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) as a binder, and 2.0 parts by mass of sodium carboxymethylcellulose (manufactured by Daicel FineChem Co., Ltd.) were added to an ethanol aqueous solution, and these were mixed for 30 minutes using a rotation / revolution mixer under conditions of revolution of 1600 rpm and rotation of 640 rpm to prepare composition A-1. Composition A-1 was prepared so that the weight ratio of solid content:solvent (ethanol aqueous solution) was 40:60, and the content of ethanol in the ethanol aqueous solution was 10% by mass.

[0175] [Example 1-2] Preparation of Composition A-2 Composition A-2 was prepared in the same manner as in Example 1-1, except that SPAN (A-1) in Example 1-1 was changed to SPAN (A-2). Composition A-2 was prepared so that the weight ratio of solids to solvent (aqueous ethanol solution) was 40:60, and the content of ethanol in the aqueous ethanol solution was 10% by mass.

[0176] [Example 1-3] Preparation of Composition A-3 Composition A-3 was prepared in the same manner as in Example 1-1, except that SPAN (A-1) in Example 1-1 was changed to SPAN (A-3). Composition A-3 was prepared so that the weight ratio of solids to solvent (aqueous ethanol solution) was 40:60, and the content of ethanol in the aqueous ethanol solution was 10% by mass.

[0177] [Example 1-4] Preparation of Composition A-4 Composition A-4 was prepared in the same manner as in Example 1-1, except that SPAN (A-1) in Example 1-1 was changed to SPAN (A-4). Composition A-4 was prepared such that the weight ratio of solids to solvent (aqueous ethanol solution) was 40:60, and the content of ethanol in the aqueous ethanol solution was 10% by mass.

[0178] [Example 1-5] Preparation of Composition A-5 Composition A-5 was prepared in the same manner as in Example 1-1, except that the ethanol aqueous solution in Example 1-1 was replaced with a 1-propanol aqueous solution. Composition A-5 was prepared so that the weight ratio of solids to solvent (1-propanol aqueous solution) was 40:60, and the content of 1-propanol in the 1-propanol aqueous solution was 10% by mass.

[0179] [Example 1-6] Preparation of Composition A-6 Composition A-6 was prepared by the same procedure as in Example 1-1, except that SPAN (A-1) was changed to SPAN (A-2) and the ethanol aqueous solution was changed to a 1-propanol aqueous solution in Example 1-1. Composition A-6 was prepared so that the weight ratio of solids to solvent (1-propanol aqueous solution) was 40:60 and the content of 1-propanol in the 1-propanol aqueous solution was 10% by mass.

[0180] [Example 1-7] Preparation of Composition A-7 Composition A-7 was prepared by the same procedure as in Example 1-1, except that SPAN (A-1) was changed to SPAN (A-3) and the ethanol aqueous solution was changed to a 1-propanol aqueous solution. Composition A-7 was prepared so that the weight ratio of solids to solvent (1-propanol aqueous solution) was 40:60 and the content of 1-propanol in the 1-propanol aqueous solution was 10% by mass.

[0181] [Example 1-8] Preparation of Composition A-8 Composition A-8 was prepared by the same procedure as in Example 1-1, except that SPAN (A-1) was changed to SPAN (A-4) and the ethanol aqueous solution was changed to a 1-propanol aqueous solution in Example 1-1. Composition A-8 was prepared so that the weight ratio of solids to solvent (1-propanol aqueous solution) was 40:60 and the content of 1-propanol in the 1-propanol aqueous solution was 10% by mass.

[0182] [Example 1-9] Preparation of Composition A-9 Composition A-9 was prepared by the same procedure as in Example 1-1, except that SPAN (A-1) was changed to SPAN (A-3) and styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) was changed to Polysol (registered trademark) LB-300 (manufactured by Showa Denko K.K.) in Example 1-1. Composition A-9 was prepared so that the weight ratio of solids to solvent (aqueous ethanol solution) was 40:60 and the content of ethanol in the aqueous ethanol solution was 10% by mass.

[0183] [Example 1-10] Preparation of Composition A-10 Composition A-10 was prepared by the same procedure as in Example 1-1, except that SPAN (A-1) was changed to SPAN (A-4) and styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) was changed to Polysol (registered trademark) LB-300 (manufactured by Showa Denko K.K.) in Example 1-1. Composition A-10 was prepared so that the weight ratio of solids to solvent (aqueous ethanol solution) was 40:60 and the content of ethanol in the aqueous ethanol solution was 10% by mass.

[0184] [Example 1-11] Preparation of Composition A-11 Composition A-11 was prepared by the same procedure as in Example 1-1, except that SPAN (A-1) was changed to SPAN (A-3) and styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) was changed to polyacrylic acid PAH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in Example 1-1. Composition A-11 was prepared so that the weight ratio of solids to solvent (aqueous ethanol solution) was 40:60 and the content of ethanol in the aqueous ethanol solution was 10% by mass.

[0185] [Example 1-12] Preparation of Composition A-12 Composition A-12 was prepared by the same procedure as in Example 1-1, except that SPAN (A-1) was changed to SPAN (A-4) and styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) was changed to polyacrylic acid PAH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in Example 1-1. Composition A-12 was prepared so that the weight ratio of solids to solvent (aqueous ethanol solution) was 40:60 and the content of ethanol in the aqueous ethanol solution was 10% by mass.

[0186] [Comparative Example 1-1] Preparation of Comparative Composition a-1 90 parts by mass of SPAN (A-1) as an active material, 5 parts by mass of acetylene black (manufactured by Denka Co., Ltd.) as a conductive assistant, 3.0 parts by mass (solid content) of styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) as a binder, and 2.0 parts by mass of sodium carboxymethylcellulose (manufactured by Daicel FineChem Co., Ltd.) were added to water, and these were mixed for 30 minutes using a rotation / revolution mixer under the conditions of revolution of 1600 rpm and rotation of 640 rpm to prepare comparative composition a-1. Comparative composition a-1 was made so that the weight ratio of solid content:solvent (water) was 40:60.

[0187] [Comparative Example 1-2] Preparation of Comparative Composition a-2 Comparative composition a-2 was prepared in the same manner as in Comparative Example 1-1, except that SPAN (A-1) was replaced with SPAN (A-2). Comparative composition a-2 had a solids:solvent (water) weight ratio of 40:60.

[0188] [Comparative Example 1-3] Preparation of Comparative Composition a-3 Comparative composition a-3 was prepared in the same manner as in Comparative Example 1-1, except that SPAN (A-1) was replaced with SPAN (A-3). Comparative composition a-3 had a solid content:solvent (water) weight ratio of 40:60.

[0189] [Comparative Example 1-4] Preparation of Comparative Composition a-4 Comparative composition a-4 was prepared in the same manner as in Comparative Example 1-1, except that SPAN (A-1) was replaced with SPAN (A-4). Comparative composition a-4 had a solids:solvent (water) weight ratio of 40:60.

[0190] [Comparative Example 1-5] Preparation of Comparative Composition a-5 As an active material, 88 parts by mass of a sulfur-carbon composite obtained by mixing sulfur and carbon nanotubes and then heat-treating them at 155°C, 5 parts by mass of vapor-grown carbon fiber (VGCF) as a conductive additive, and 7 parts by mass of polyacrylic acid PAH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) as a binder were added to a 1-propanol aqueous solution, and these were mixed for 30 minutes using a rotation-revolution mixer under conditions of 1600 rpm revolution and 640 rpm rotation to prepare a comparative composition a-5. The comparative composition a-5 was prepared so that the weight ratio of solids to solvent (1-propanol aqueous solution) was 23:77, and the content of 1-propanol in the 1-propanol aqueous solution was 13% by mass.

[0191] [Comparative Example 1-6] Preparation of Comparative Composition a-6 Comparative composition a-6 was prepared in the same manner as in Comparative Example 1-5, except that the 1-propanol aqueous solution was replaced with water. Comparative composition a-6 had a solids:solvent (water) weight ratio of 23:77.

[0192] [Comparative Example 1-7] Preparation of Comparative Composition a-7 Comparative composition a-7 was prepared in the same manner as in Comparative Example 1-1, except that SPAN (A-1) was changed to SPAN (A-3) and styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) was changed to Polysol (registered trademark) LB-300 (trade name manufactured by Showa Denko K.K.) in Comparative Example 1-1. Comparative composition a-7 was prepared so that the weight ratio of solid content:solvent (water) was 40:60.

[0193] [Comparative Example 1-8] Preparation of Comparative Composition a-8 Comparative composition a-8 was prepared in the same manner as in Comparative Example 1-1, except that SPAN (A-1) was changed to SPAN (A-4) and styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) was changed to Polysol (registered trademark) LB-300 (trade name manufactured by Showa Denko K.K.) in Comparative Example 1-1. Comparative composition a-8 was prepared so that the weight ratio of solid content:solvent (water) was 40:60.

[0194] [Comparative Example 1-9] Preparation of Comparative Composition a-9 Comparative composition a-9 was prepared in the same manner as in Comparative Example 1-1, except that SPAN (A-1) was changed to SPAN (A-3) and styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) was changed to polyacrylic acid PAH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). Comparative composition a-9 was prepared so that the weight ratio of solid content:solvent (water) was 40:60.

[0195] [Comparative Example 1-10] Preparation of Comparative Composition a-10 Comparative composition a-10 was prepared in the same manner as in Comparative Example 1-1, except that SPAN (A-1) was changed to SPAN (A-4) and styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) was changed to polyacrylic acid PAH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). Comparative composition a-10 was prepared so that the weight ratio of solid content:solvent (water) in Comparative Example a-10 was 40:60.

[0196] [Example 2-1] Production of electrode A-1 The composition A-1 obtained in Example 1-1 was applied by a doctor blade method to one side of a current collector made of carbon-coated aluminum foil (thickness 22 μm), and the current collector was left to stand and dry at 80° C. for 1 hour, and then press-molded. Thereafter, the aluminum foil applied to the current collector was cut to a predetermined size (circular shape), and further vacuum-dried at 130° C. for 2 hours immediately before use to prepare an electrode A-1.

[0197] [Example 2-2] Production of electrode A-2 An electrode A-2 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-2.

[0198] [Example 2-3] Production of electrode A-3 An electrode A-3 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-3.

[0199] [Example 2-4] Production of electrode A-4 An electrode A-4 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-4.

[0200] [Example 2-5] Production of electrode A-5 An electrode A-5 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-5.

[0201] [Example 2-6] Production of electrode A-6 An electrode A-6 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-6.

[0202] [Example 2-7] Production of electrode A-7 An electrode A-7 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-7.

[0203] [Example 2-8] Production of electrode A-8 An electrode A-8 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-8.

[0204] [Example 2-9] Production of electrode A-9 An electrode A-9 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-9.

[0205] [Example 2-10] Production of electrode A-10 An electrode A-10 was produced in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-10.

[0206] [Example 2-11] Production of electrode A-11 An electrode A-11 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-11.

[0207] [Example 2-12] Production of electrode A-12 An electrode A-12 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the composition A-12.

[0208] [Comparative Example 2-1] Production of electrode a-1 An electrode a-1 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the comparative composition a-1.

[0209] [Comparative Example 2-2] Production of electrode a-2 An electrode a-2 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the comparative composition a-2.

[0210] [Comparative Example 2-3] Production of electrode a-3 An electrode a-3 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the comparative composition a-3.

[0211] [Comparative Example 2-4] Production of electrode a-4 An electrode a-4 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the comparative composition a-4.

[0212] [Comparative Example 2-5] Production of electrode a-5 An electrode a-5 was prepared in the same manner as in Example 2-1, except that composition A-1 in Example 2-1 was changed to comparative composition a-5, and the conditions of vacuum drying at 130°C for 2 hours were changed to vacuum drying at 70°C for 2 hours.

[0213] [Comparative Example 2-6] Production of electrode a-6 An electrode a-6 was prepared in the same manner as in Example 2-1, except that composition A-1 in Example 2-1 was changed to comparative composition a-6, and the conditions of vacuum drying at 130°C for 2 hours were changed to vacuum drying at 70°C for 2 hours.

[0214] [Comparative Example 2-7] Production of electrode a-7 An electrode a-7 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the comparative composition a-7.

[0215] [Comparative Example 2-8] Production of electrode a-8 An electrode a-8 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the comparative composition a-8.

[0216] [Comparative Example 2-9] Production of electrode a-9 An electrode a-9 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the comparative composition a-9.

[0217] [Comparative Example 2-10] Production of electrode a-10 An electrode a-10 was prepared in the same manner as in Example 2-1, except that the composition A-1 in Example 2-1 was changed to the comparative composition a-10.

[0218] [Example 3-1] Production of lithium-ion secondary battery The electrode A-1 produced in Example 2-1 was used as the working electrode, and the counter electrode was a 500 μm thick lithium metal cut into a circular shape, and the separator was a glass filter sandwiched between the working electrode and the counter electrode and held in the case. A non-aqueous electrolyte prepared by mixing 50% by volume of ethylene carbonate and 50% by volume of diethyl carbonate with LiPF6 at a concentration of 1.0 ml / L was sealed in the case, and the case was sealed using a crimping machine to produce a coin-shaped lithium ion secondary battery A with a diameter of 20 mm and a thickness of 3.2 mm. The capacity of the battery was 3 mAh.

[0219] [Example 3-2] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-2 produced in Example 2-2. The capacity of the battery was 3 mAh.

[0220] [Example 3-3] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-3 produced in Example 2-3. The capacity of the battery was 3 mAh.

[0221] [Example 3-4] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-4 produced in Example 2-4. The capacity of the battery was 3 mAh.

[0222] [Example 3-5] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-5 produced in Example 2-5. The capacity of the battery was 3 mAh.

[0223] [Examples 3-6] Production of lithium-ion secondary batteries A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-6 produced in Example 2-6. The capacity of the battery was 3 mAh.

[0224] [Example 3-7] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-7 produced in Example 2-7. The capacity of the battery was 3 mAh.

[0225] [Example 3-8] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-8 produced in Example 2-8. The capacity of the battery was 3 mAh.

[0226] [Example 3-9] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-9 produced in Example 2-9. The capacity of the battery was 3 mAh.

[0227] [Example 3-10] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-10 produced in Example 2-10. The capacity of the battery was 3 mAh.

[0228] [Example 3-11] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-11 produced in Example 2-11. The capacity of the battery was 3 mAh.

[0229] [Example 3-12] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-12 produced in Example 2-12. The capacity of the battery was 3 mAh.

[0230] [Example 3-13] Production of lithium-ion secondary battery The electrode A-1 produced in Example 2-1 was used as the working electrode, a 500 μm thick lithium metal cut into a circular shape was used as the counter electrode, and a polyethylene oxide-based polymer nonaqueous electrolyte H-Polymer (NEI Corporation) was used as the solid electrolyte. The solid electrolyte was impregnated into the working electrode, placed between the working electrode and the counter electrode, and the case was sealed using a crimping machine to produce a coin-shaped lithium ion secondary battery with a diameter of 20 mm and a thickness of 3.2 mm. The capacity of the battery was 3 mAh.

[0231] [Example 3-14] Production of lithium-ion secondary battery A coin lithium ion secondary battery was produced in the same manner as in Example 3-13, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode A-2 produced in Example 2-2. The capacity of the battery was 3 mAh.

[0232] [Comparative Example 3-1] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-1 produced in Comparative Example 2-1. The capacity of the battery was 3 mAh.

[0233] [Comparative Example 3-2] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-2 produced in Comparative Example 2-2. The capacity of the battery was 3 mAh.

[0234] [Comparative Example 3-3] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-3 produced in Comparative Example 2-3. The capacity of the battery was 3 mAh.

[0235] [Comparative Example 3-4] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-4 produced in Comparative Example 2-4. The capacity of the battery was 3 mAh.

[0236] [Comparative Example 3-5] Manufacture of lithium ion secondary battery The working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-5 produced in Comparative Example 2-5, and the non-aqueous electrolyte was changed from a mixed solvent of 50% by volume of ethylene carbonate and 50% by volume of diethyl carbonate, with LiPF6 at a concentration of 1.0 ml / L, to a mixed solvent of 50% by volume of dioxolane and 50% by volume of dimethoxyethane, with LiN(CF3SO2)2 at a concentration of 1.0 ml / L, with 1% by weight of LiNO3 added. A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1. The capacity of the battery was 3 mAh.

[0237] [Comparative Example 3-6] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Comparative Example 3-5, except that the working electrode was changed from the electrode a-5 produced in Comparative Example 2-5 to the electrode a-6 produced in Comparative Example 2-6. The capacity of the battery was 3 mAh.

[0238] [Comparative Example 3-7] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-7 produced in Comparative Example 2-7. The capacity of the battery was 3 mAh.

[0239] [Comparative Example 3-8] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-8 produced in Comparative Example 2-8. The capacity of the battery was 3 mAh.

[0240] [Comparative Example 3-9] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-9 produced in Comparative Example 2-9. The capacity of the battery was 3 mAh.

[0241] [Comparative Example 3-10] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-1, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-10 produced in Comparative Example 2-10. The capacity of the battery was 3 mAh.

[0242] [Comparative Example 3-11] Manufacture of lithium ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-13, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-1 produced in Comparative Example 2-1. The capacity of the battery was 3 mAh.

[0243] [Comparative Example 3-12] Production of lithium-ion secondary battery A coin-type lithium ion secondary battery was produced in the same manner as in Example 3-13, except that the working electrode was changed from the electrode A-1 produced in Example 2-1 to the electrode a-2 produced in Comparative Example 2-2. The capacity of the battery was 3 mAh.

[0244] The lithium ion secondary batteries produced in Examples 3-1 to 3-14 and Comparative Examples 3-1 to 3-12 were used to carry out the following evaluations.

[0245] (1) Coatability The surface condition of the working electrode was observed under a microscope. If the entire surface of the working electrode was smooth, it was evaluated as "Good." If the entire surface of the working electrode was uneven, it was evaluated as "NG." If only part of the surface of the working electrode was uneven, it was evaluated as "Poor." The results are shown in Table 2.

[0246] (2) Cycle capacity retention rate The lithium ion secondary batteries produced in Examples 3-1 to 3-12 and Comparative Examples 3-1 to 3-10 were used to evaluate cycle capacity retention rates (%) by the following method. The lithium-ion secondary battery was placed in a thermostatic chamber at 25°C, and a charge / discharge test was performed 10 times in succession under the conditions of a charge rate of 0.1C and a discharge rate of 0.1C, with a charge end voltage of 3.0V and a discharge end voltage of 1.0V. Then, a charge test was performed 100 times in succession under the conditions of a charge rate of 0.5C and a discharge rate of 0.5C, for a total of 110 charge / discharge tests, and the discharge capacity was measured. The ratio of the 15th discharge capacity / the 110th discharge capacity was calculated as the cycle capacity retention rate (%). The results are shown in Table 2.

[0247] The lithium ion secondary batteries produced in Examples 3-13, 3-14, Comparative Examples 3-11, and 3-12 were used to evaluate cycle capacity retention rates (%) by the following method. The lithium-ion secondary battery was placed in a thermostatic chamber at 60°C, and a charge / discharge test was carried out 50 times in succession under the conditions of a charge cut-off voltage of 3.0V, a discharge cut-off voltage of 1.0V, a charge rate of 0.1C, and a discharge rate of 0.1C, to measure the discharge capacity. The ratio of the 5th discharge capacity to the 50th discharge capacity was calculated as the cycle capacity retention rate (%). The results are shown in Table 2.

[0248] [Table 2]

[0249] The abbreviations of the components listed in Table 2 are as follows. (1)Active material A-1: SPAN (A-1) A-2: SPAN (A-2) A-3: SPAN (A-3) A-4: SPAN (A-4) Carbon-sulfur composite: Obtained by heat-treating a mixture of sulfur and carbon nanotubes (2) Binder SBR: Styrene-butadiene rubber (40% by mass aqueous dispersion, manufactured by Zeon Corporation) CMC: Sodium carboxymethylcellulose (manufactured by Daicel FineChem Co., Ltd.) LB-300: Polysol (registered trademark) LB-300 (manufactured by Showa Denko K.K.) PAH: Polyacrylic acid PAH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (3) Conductive additives AB: Acetylene black (manufactured by Denka Co., Ltd.) VGCF: Vapor grown carbon fiber (4) Alcohol EtOH: Ethanol PrOH: 1-propanol (5) Electrolyte Liquid A: A non-aqueous electrolyte prepared by mixing 50% by volume of ethylene carbonate and 50% by volume of diethyl carbonate with LiPF6 at a concentration of 1.0 ml / L. Liquid B: A non-aqueous electrolyte prepared by mixing 50% by volume of dioxolane and 50% by volume of dimethoxyethane with LiN(CF3SO2)2 at a concentration of 1.0 ml / L and adding 1% by weight of LiNO3. Solid: Solid electrolyte {polyethylene oxide-based polymeric non-aqueous electrolyte H-Polymer (NEI Corporation)}

[0250] From the results in Table 2, in Comparative Examples 3-1 to 3-12, the coating properties of the compositions used to form the electrode active material layers were insufficient, and the cycle capacity retention rates of the manufactured lithium ion secondary batteries were insufficient in some cases. In contrast, in Examples 3-1 to 3-14, the coating properties of the compositions used to form the electrode active material layers were good, and the cycle capacity retention rates of the manufactured lithium ion secondary batteries were at a high level, that is, it was confirmed that there was little decrease in charge / discharge capacity even after repeated charge / discharge. [Explanation of symbols]

[0251] 1 SPAN-containing electrode active material layer 1a Positive electrode current collector 2 Negative electrode active material layer 2a Negative electrode current collector 3. Nonaqueous electrolyte 4. Positive electrode case of external packaging 5. External packaging negative electrode case 6 Gasket 7 Separator 10. Coin-type lithium-ion secondary battery 10' Cylindrical lithium-ion secondary battery 11 Negative electrode active material layer 12 Negative electrode current collector 13 SPAN-containing electrode active material layer 14 Positive electrode current collector 15. Nonaqueous electrolytes 16 Separator 17 Positive terminal 18 Negative terminal 19 Negative plate 20 Negative lead 21 Positive electrode plate 22 Positive lead 23 cases 24 Insulating plate 25 Gasket 26 Safety valve 27 PTC element 28 Laminated lithium-ion secondary battery 29 Electrode group 30 Laminate film on the case side of the outer packaging 31 Laminate film on the lid side of the outer packaging

Claims

1. A composition comprising sulfur-modified polyacrylonitrile, alcohol and water, wherein the content of the alcohol is 0.1% by mass to 50% by mass based on the total amount of the alcohol and water.

2. The composition according to claim 1, wherein the alcohol is an alcohol having 1 to 5 carbon atoms.

3. The composition according to claim 1 or 2, comprising 15 to 70 parts by mass of the sulfur-modified polyacrylonitrile and 30 to 80 parts by mass of the alcohol and the water in total, per 100 parts by mass of the composition.

4. The composition according to any one of claims 1 to 3, further comprising 0.1 to 30 parts by mass of a conductive assistant per 100 parts by mass of the composition.

5. The composition according to any one of claims 1 to 4, further comprising 0.2 parts by mass to 18 parts by mass of a binder in 100 parts by mass of the composition.

6. The composition of claim 5, wherein the binder is a water-based binder.

7. The composition according to any one of claims 1 to 6, which is for forming an electrode active material layer.

8. An electrode having an electrode active material layer formed using the composition according to claim 7.

9. A battery comprising the electrode according to claim 8, a counter electrode, and a non-aqueous electrolyte.

10. An electrode active material comprising sulfur-modified polyacrylonitrile, It is added to a composition containing alcohol and water, The content of the alcohol in the composition is 0.1% by mass to 50% by mass with respect to the total of the alcohol and the water.

Citation Information

Patent Citations

  • Electrode slurry composition for lithium ion storage devices

    JP2020527827A

  • Positive electrode slurry composition, positive electrode prepared using the same, and battery including the same

    JP2021509529A